Compound, hole transport material for photoelectric conversion element, hole transport layer, and photoelectric conversion element and solar cell using the same
Patent Information
- Application Number
- CN202180059231.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-30
- Filing Date
- 2021-07-27
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2041-07-27
AI Technical Summary
[0005]但是,使用作为添加剂的掺杂剂时,担心会降低使用了有机化合物的光电转换元件的耐久性而缩短元件整体的寿命(例如,非专利文献3),因此期望开发具有不包含掺杂剂或降低了掺杂剂含量的空穴传输层的光电转换元件
[0032]根据本发明涉及的化合物及含有该化合物的光电转换元件用空穴传输材料,能够制作高耐久性的光电转换元件及太阳能电池。
Smart Images

Figure CN116157406B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to compounds, hole transport materials for photoelectric conversion elements, hole transport layers, and photoelectric conversion elements and solar cells using the same. Background Technology
[0002] In recent years, solar power generation, as a clean energy source, has attracted much attention, and the development of solar cells has become increasingly popular. Among them, the development of perovskite solar cells (hereinafter referred to as perovskite solar cells), which are low-cost and can be manufactured using solution processes, is attracting attention (e.g., Patent Document 1, Non-Patent Documents 1-2).
[0003] Perovskite solar cells mostly use hole transport materials in their elements. Examples of their use include: (1) improving the selective transport of holes to increase photoelectric conversion efficiency; and (2) protecting the perovskite material, which is susceptible to moisture and oxygen, by bonding it to the perovskite photoelectric conversion layer (e.g., Non-Patent Literature 3). Spiro-OMeTAD, a spirodifluorene-based organic compound, is a standard hole transport material, but there are few reports of hole transport materials that contribute to improved photoelectric conversion characteristics using this material.
[0004] When hole transport materials are used in elements of perovskite solar cells, in conventional methods that use organic compounds to fabricate elements, a dopant is added to the hole transport material as an additive. This dopant is used to reduce the resistance of the hole transport material (e.g., Non-Patent Literature 3-4).
[0005] However, there are concerns that using dopants as additives may reduce the durability of photoelectric conversion elements using organic compounds and shorten the overall lifespan of the element (e.g., Non-Patent Document 3). Therefore, it is desirable to develop photoelectric conversion elements with hole transport layers that do not contain dopants or have reduced dopant content. In addition, if dopants are absent or their content is reduced, additive costs or manufacturing process costs can be reduced.
[0006] Patent Document 1: International Publication No. 2017 / 104792
[0007] Non-patent literature 1: Journal of the American Chemical Society, 2009, Vol. 131, pp. 6050-6051
[0008] Non-patent literature 2: Science, 2012, Vol. 388, pp. 643-647
[0009] Non-patent literature 3: Chem. Sci., 2019, 10, pp. 6748-6769
[0010] Non-patent literature 4: Adv. Funct. Mater., 2019, 1901-296 Summary of the Invention
[0011] The problem to be solved by the present invention is to provide a novel hole transport material for photoelectric conversion elements that can be used to form photoelectric conversion elements and solar cells with high durability, and a photoelectric conversion element and solar cell using the same.
[0012] To address the aforementioned issues, the inventors conducted in-depth research and discovered that by using compounds with specific structures as hole transport materials for photoelectric conversion elements, highly durable photoelectric conversion elements and solar cells can be obtained. In other words, the main contents of this invention are as follows.
[0013] 1. A compound represented by the following general formula (1), wherein X in general formula (1) 1 and X 2 Each is represented independently by the following general formula (2).
[0014] [Chemical Formula 1]
[0015]
[0016] [In the formula, R] 1 and R 2 Each of the following can be independently represented: a nitrile group, a straight-chain or branched perfluoroalkyl group having 1 to 4 carbon atoms, a straight-chain or branched acyl group having 1 to 18 carbon atoms that can have substituents, a straight-chain or branched alkoxycarbonyl group having 1 to 18 carbon atoms that can have substituents, a thio group having 1 to 18 carbon atoms that can have substituents, an amino group having 1 to 20 carbon atoms that can have substituents, or a straight-chain or branched alkylsulfonyl group having 1 to 18 carbon atoms that can have substituents.
[0017] R 3 ~R 22Each of the following groups can independently represent a hydrogen atom, a halogen atom, a carboxyl group, a trimethylsilyl group, a straight-chain or branched alkyl group with 1 to 18 carbon atoms that can have substituents, a straight-chain or branched alkenyl group with 2 to 20 carbon atoms that can have substituents, a straight-chain or branched alkynyl group with 2 to 20 carbon atoms that can have substituents, a cycloalkyl group with 3 to 10 carbon atoms that can have substituents, a straight-chain or branched alkoxy group with 1 to 20 carbon atoms that can have substituents, a cycloalkoxy group with 3 to 10 carbon atoms that can have substituents, an acyl group with 1 to 20 carbon atoms that can have substituents, a thio group with 1 to 18 carbon atoms that can have substituents, an amino group with 1 to 20 carbon atoms that can have substituents, an aromatic hydrocarbon group with 6 to 36 carbon atoms that can have substituents, or a heterocyclic group with 5 to 36 cyclic atoms that can have substituents.
[0018] R 1 and R 2 They can bond together to form a ring, R 3 ~R 7 R 8 ~R 12 R 13 ~R 17 and R 18 ~R 22 Adjacent groups in R can bond with each other to form a ring. 7 With R 8 and R 17 With R 18 They can bond together to form a ring.
[0019] Among them, in R 1 and R 2 It is a nitrile group, R 5 In the case of methoxy group, R 10 R 15 R 20 At least one of the groups is one of the aforementioned groups other than methoxy.
[0020] [Chemical Formula 2]
[0021]
[0022] [In the formula, R] 23 ~R 28Each of the following groups can independently represent a hydrogen atom, a straight-chain or branched alkyl group with 1 to 20 carbon atoms that can have substituents, a straight-chain or branched alkenyl group with 2 to 20 carbon atoms that can have substituents, a straight-chain or branched alkynyl group with 2 to 20 carbon atoms that can have substituents, a cycloalkyl group with 3 to 10 carbon atoms that can have substituents, a straight-chain or branched alkoxy group with 1 to 20 carbon atoms that can have substituents, a cycloalkoxy group with 3 to 10 carbon atoms that can have substituents, a thio group with 1 to 18 carbon atoms that can have substituents, an amino group with 1 to 20 carbon atoms that can have substituents, an aromatic hydrocarbon group with 6 to 36 carbon atoms that can have substituents, or a heterocyclic group with 5 to 36 cyclic atoms that can have substituents.
[0023] R 23 With R 24 R 25 With R 26 and R 27 With R 28 They can bond together to form a ring.
[0024] Y 1 It represents an oxygen atom, a sulfur atom, or a selenium atom, where m and n represent integers from 0 to 2.
[0025] Where either m or n is 1 or 2.
[0026] 2. The compound according to 1 above, wherein, in the general formula (1), R 1 and R 2 Each can be independently a nitrile group, a straight-chain or branched acyl group having 1 to 18 carbon atoms that can have a substituent, or a straight-chain or branched alkoxycarbonyl group having 1 to 18 carbon atoms that can have a substituent.
[0027] 3. The compound according to 1 or 2 above, wherein m in the general formula (2) is 1.
[0028] 4. A hole transport material for a photoelectric conversion element, comprising any one of the compounds described in 1 to 3 above.
[0029] 5. A hole transport layer formed of a composition comprising a hole transport material for a photoelectric conversion element as described in 4 above and a dopant as an additive, wherein the dopant is in an equivalent amount of 0 to 0.5 equivalents relative to the hole transport material for the photoelectric conversion element 1.
[0030] 6. A photoelectric conversion element comprising the hole transport material for the photoelectric conversion element described in 5 above.
[0031] 7. A solar cell comprising the photoelectric conversion element described in 6 above.
[0032] According to the compound involved in this invention and the hole transport material for photoelectric conversion elements containing the compound, it is possible to manufacture photoelectric conversion elements and solar cells with high durability. Attached Figure Description
[0033] Figure 1 This is a first schematic cross-sectional view showing the configuration of the photoelectric conversion element of the embodiments and comparative examples of the present invention.
[0034] Figure 2 This is a second schematic cross-sectional view showing the configuration of the photoelectric conversion element in the embodiments and comparative examples of the present invention. Detailed Implementation
[0035] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. The hole transport material for photoelectric conversion elements of the present invention is used in photoelectric conversion elements and solar cells.
[0036] <Photoelectric conversion element>
[0037] like Figure 1 As shown in the first schematic cross-sectional view, a typical example of the photoelectric conversion element of the present invention includes a conductive support 1, a hole blocking layer 2, an electron transport layer 3, a photoelectric conversion layer 4, a hole transport layer 5, and a counter electrode 6. Additionally, as... Figure 2 As shown in the second schematic cross-sectional view, another typical example of the photoelectric conversion element of the present invention has a conductive support 7, an electron transport layer 8, a photoelectric conversion layer 9, a hole transport layer 10, and a counter electrode 11.
[0038] Hereinafter, compounds represented by general formula (1) will be specifically described as hole transport materials for photoelectric conversion elements of the present invention, but the present invention is not limited to these compounds.
[0039] A compound represented by general formula (1), wherein R 1 and R 2 Each of the following groups can be independently represented: a nitrile group, a straight-chain or branched perfluoroalkyl group having 1 to 4 carbon atoms, a straight-chain or branched acyl group having 1 to 18 carbon atoms that can have substituents, a straight-chain or branched alkoxycarbonyl group having 1 to 18 carbon atoms that can have substituents, a thio group having 1 to 18 carbon atoms that can have substituents, an amino group having 1 to 20 carbon atoms that can have substituents, or a straight-chain or branched alkylsulfonyl group having 1 to 18 carbon atoms that can have substituents, preferably electron-withdrawing.
[0040] In this invention, fluorine, chlorine, bromine and iodine can be listed as "halogen atoms".
[0041] In general formula (1), as R 1 R 2The term "perfluoroalkyl group with 1 to 4 carbon atoms in a straight or branched form" specifically includes, for example, methyl, ethyl, n-propyl, and n-butyl, in which the hydrogen atoms in a straight or branched alkyl group with 1 to 4 carbon atoms are completely replaced by fluorine atoms (perfluorination).
[0042] In general formula (1), as R 1 R 2 The phrase "a straight-chain or branched acyl group with 1 to 20 carbon atoms capable of having substituents" specifically includes acetyl, propionyl, butyryl, isobutyryl, valeryl, isovaleryl, benzoylacetyl, benzoyl, etc. In cases involving alkyl chains, this includes situations where all hydrogen atoms are replaced by fluorine atoms (perfluorination). Additionally, it can also include cases where it is bonded to an amino group (-CO-N < ).
[0043] In general formula (1), as R 1 R 2 The phrase "a straight-chain or branched alkoxycarbonyl group with 1 to 18 carbon atoms capable of having substituents" specifically includes, for example, methoxycarbonyl, ethoxycarbonyl, etc., and in the case of an alkyl chain, includes cases where the hydrogen atoms are completely replaced by fluorine atoms (perfluorination).
[0044] In general formula (1), as R 1 R 2 The phrase "thiogroup with 1 to 18 carbon atoms that can have substituents" specifically includes, for example, methylthio, ethylthio, propylthio, phenylthio, biphenylthio, etc.
[0045] In general formula (1), as R 1 R 2 The phrase "amino group with 1 to 20 carbon atoms that can have substituents" specifically includes, as a monosubstituted amino group, ethylamino, acetylamino, phenylamino, etc., and as a disubstituted amino group, diethylamino, diphenylamino, acetylphenylamino, etc.
[0046] In general formula (1), as R 1 R 2 The phrase "a straight-chain or branched alkyl sulfonyl group with 1 to 18 carbon atoms capable of having substituents" specifically refers to an alkyl sulfonyl group consisting of -SO2A... 1 (A 1The group represented by (an alkyl group having 1 to 18 carbon atoms in a straight-chain or branched alkyl group having 1 to 20 carbon atoms that can have substituents) is designated as A. 1 Examples of such substituents include methyl, ethyl, n-propyl, and n-butyl, which are straight-chain or branched alkyl groups having 1 to 20 carbon atoms.
[0047] In general formula (1), as R 1 R 2 The term "substituent" in the following contexts refers to "acyl group having 1 to 20 carbon atoms that can have a substituent," "linear or branched alkoxycarbonyl group having 1 to 18 carbon atoms that can have a substituent," "thio group having 1 to 18 carbon atoms that can have a substituent," "amino group having 1 to 20 carbon atoms that can have a substituent," or "linear or branched alkylsulfonyl group having 1 to 18 carbon atoms that can have a substituent." Specifically, examples include:
[0048] Halogen atoms such as fluorine, chlorine, bromine, and iodine; cyano group; hydroxyl group; nitro group; nitroso group; carboxyl group; phosphate group; thio group (>C=S);
[0049] Carboxylic acid ester groups such as methyl ester group and ethyl ester group;
[0050] Alkyl groups with 1 to 18 carbon atoms, including methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, n-hexyl, 2-ethylhexyl, heptyl, octyl, isooctyl, nonyl, and decyl.
[0051] Alkenes with 2 to 20 carbon atoms, including vinyl, 1-propenyl, 2-propenyl (allyl), 1-butenyl, 2-butenyl, 1-pentenyl, 1-hexenyl, 2-methyl-1-propenyl, 2-methyl-2-propenyl, and 1-ethyl vinyl, are straight-chain or branched alkenyl groups.
[0052] Alkoxy groups with 1 to 18 carbon atoms, such as methoxy, ethoxy, propoxy, tert-butoxy, pentoxy, and hexoxy, are straight-chain or branched alkoxy groups.
[0053] Aromatic hydrocarbon groups with 6 to 30 carbon atoms, such as phenyl, naphthyl, anthraceneyl, phenanthryl, and pyrene;
[0054] Heterocyclic groups with 5 to 30 cyclic atoms, including pyridyl, pyrimidinyl, triazinyl, thiopheneyl, furanyl, pyrrolithyl, imidazolyl, pyrazolyl, triazolyl, quinolinyl, isoquinolinyl, naphridyl, acridineyl, phenanthrololinyl, benzofuranyl, benzothiopheneyl, oxazolyl, indolyl, carbazolyl, benzooxazolyl, thiazolyl, benzothiazolyl, quinoxolinyl, benzoimidazolyl, pyrazolyl, dibenzofuranyl, dibenzothiopheneyl, and carbazolyl.
[0055] Amino groups with 0 to 18 carbon atoms that are monosubstituted amino groups such as unsubstituted amino groups (―NH2), ethylamino, acetylamino, phenylamino, etc., or disubstituted amino groups such as diethylamino, diphenylamino, acetylphenylamino, etc.
[0056] Unsubstituted thiols (thiols: ―SH), methylthiols, ethylthiols, propylthiols, phenylthiols, biphenylthiols, and other thiols with 0 to 18 carbon atoms; etc.
[0057] These "substituents" may include only one type or multiple types, and when multiple types are included, they may be the same as or different from each other. In addition, these "substituents" may further have the substituents exemplified above.
[0058] In general formula (1), R 1 and R 2 They can bond with each other to form rings, which can be achieved through single bonds, bonds of oxygen atoms, sulfur atoms, selenium atoms, or bonds of nitrogen atoms. In this case, it is preferred that the rings are formed through single bonds. Furthermore, acidic heterocycles such as barbiturates, thiobarbiturates, rhodanine, thiohydantoins, and indanediones are even more preferred.
[0059] In general formula (1), R 3 ~R 22 Each of the following groups can be independently represented: hydrogen atom, halogen atom, carboxyl group, trimethylsilyl group, alkyl group with 1 to 18 carbon atoms that can have substituents (linear or branched), alkenyl group with 2 to 20 carbon atoms that can have substituents (linear or branched), alkynyl group with 2 to 20 carbon atoms that can have substituents (linear or branched), cycloalkyl group with 3 to 10 carbon atoms that can have substituents (linear or branched), alkoxy group with 1 to 20 carbon atoms that can have substituents (cycloalkoxy group with 3 to 10 carbon atoms), acyl group with 1 to 20 carbon atoms that can have substituents (acyl), thio group with 1 to 18 carbon atoms that can have substituents (thio), amino group with 1 to 20 carbon atoms that can have substituents (amino), aromatic hydrocarbon group with 6 to 36 carbon atoms that can have substituents (aromatic), or heterocyclic group with 5 to 36 cyclic atoms that can have substituents (cycloforming).
[0060] In this invention, fluorine, chlorine, bromine and iodine can be listed as "halogen atoms".
[0061] In general formula (1), as R 3 ~R 22 The phrase "a straight-chain or branched alkyl group having 1 to 20 carbon atoms that can have substituents" specifically includes methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, n-hexyl, 2-ethylhexyl, heptyl, octyl, isooctyl, nonyl, decyl, etc.
[0062] In general formula (1), as R 3 ~R 22 The phrase "alkenyl groups with 2 to 20 carbon atoms that can have substituents" specifically includes vinyl, 1-propenyl, 2-propenyl (allyl), 1-methylvinyl, 1-butenyl, 2-butenyl, 1-pentenyl, 1-hexenyl, 2-methyl-1-propenyl, 2-methyl-2-propenyl, 1-ethylvinyl, or alkenyl groups with 2 to 20 carbon atoms formed by bonding multiple of these alkenyl groups.
[0063] In general formula (1), as R 3 ~R 22 The phrase "a straight-chain or branched alkynyl group with 2 to 20 carbon atoms that can have substituents" specifically includes ethynyl, 1-propynyl, 2-propynyl, 1-butynyl, 2-butynyl, 1-methyl-2-propynyl, 1-pentynyl, 2-pentynyl, 1-methyl-n-butynyl, 2-methyl-n-butynyl, 3-methyl-n-butynyl, 1-hexynyl, etc.
[0064] In general formula (1), as R 3 ~R 22 The phrase "cycloalkyl group with 3 to 10 carbon atoms that can have substituents" specifically includes cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclodecyl, cyclododecyl, 4-methylcyclohexyl, 4-ethylcyclohexyl, etc.
[0065] In general formula (1), as R 3 ~R 22The phrase "a straight-chain or branched alkoxy group with 1 to 20 carbon atoms that can have substituents" specifically includes methoxy, ethoxy, propoxy, n-butoxy, n-pentoxy, n-hexoxy, heptoxy, octoxy, nonoxy, decoxy, isopropoxy, isobutoxy, sec-butoxy, tert-butoxy, isooctoxy, tert-octoxy, phenoxy, toluoxy, biphenyloxy, terphenyloxy, naphthoxy, anthraquinoneoxy, phenanthroxy, fluorenoxy, indoxy, etc.
[0066] In general formula (1), as R 3 ~R 22 The phrase "a straight-chain or branched cycloalkoxy group with 3 to 10 carbon atoms that can have substituents" specifically includes cyclopropoxy, cyclobutoxy, cyclopentoxy, cyclohexoxy, 4-methylcyclohexoxy, etc.
[0067] In general formula (1), as R 3 ~R 22 The "acyl group with 1 to 20 carbon atoms" in the expression "acyl group capable of having substituents" can be listed as R in general formula (1). 1 R 2 The same group as "acyl group that can have 1 to 20 carbon atoms that are substituent".
[0068] In general formula (1), as R 3 ~R 22 The "thiogroup with 1 to 18 carbon atoms" in the phrase "thiogroup capable of having substituents" can be exemplified by R in general formula (1). 1 R 2 The same group as "thiogroup with 1 to 18 carbon atoms that can have substituents".
[0069] In general formula (1), as R 3 ~R 22 The "amino group with 1 to 20 carbon atoms" in the phrase "amino group capable of having substituents" can be exemplified by those derived from R in general formula (1). 1 R 2 The same group as "an amino group that can have 1 to 20 carbon atoms that are substituents".
[0070] In general formula (1), as R 3 ~R 22The phrase "aromatic hydrocarbon groups with 6 to 36 carbon atoms capable of having substituents" specifically includes, for example, phenyl, biphenyl, terphenyl, naphthyl, biphenyl, anthraceneyl, phenanthrene, fluorenyl, indene, pyrene, perylene, fluoranyl, benzo[a]phenanthrene, etc. It should be noted that the aromatic hydrocarbon groups in this invention include "fused polycyclic aromatic hydrocarbon groups".
[0071] In general formula (1), as R 3 ~R 22 The phrase "heterocyclic groups with 5 to 36 cyclic atoms capable of having substituents" specifically includes pyridyl, pyrimidinyl, triazine, thiophene, furanyl (furanyl), pyrroloyl, imidazolyl, pyrazolyl, triazolyl, quinolinyl, isoquinolinyl, naphridyl, acridineyl, phenanthrolinel, benzofuranyl, benzothiophene, oxazolyl, indolyl, carbazolyl, benzooxazolyl, thiazolyl, benzothiazolyl, quinoxolinyl, benzoimidazolyl, pyrazolyl, dibenzofuranyl, dibenzothiophene, carbazolyl, etc.
[0072] In general formula (1), as R 3 ~R 22 The terms "alkyl group with 1 to 18 carbon atoms that can have substituents, either straight-chain or branched," "alkenyl group with 2 to 20 carbon atoms that can have substituents," "alkynyl group with 2 to 20 carbon atoms that can have substituents," "cycloalkyl group with 3 to 10 carbon atoms that can have substituents," "alkoxy group with 1 to 20 carbon atoms that can have substituents," "cycloalkoxy group with 3 to 10 carbon atoms that can have substituents," and "cycloalkoxy group with 3 to 10 carbon atoms that can have substituents" are used to describe alkyl groups with 1 to 20 carbon atoms that can have substituents, or cycloalkoxy groups with 3 to 10 carbon atoms that can have substituents. The "substituent" in the following categories can be the same as the "substituent" in "acyl group with 1 to 20 carbon atoms", "thio group with 1 to 18 carbon atoms that can have a substituent", "amino group with 1 to 20 carbon atoms that can have a substituent", "aromatic hydrocarbon group with 6 to 36 carbon atoms that can have a substituent" or "heterocyclic group with 5 to 36 cyclic atoms that can have a substituent".
[0073] In general formula (1), R 3 ~R 7 R 8 ~R 12 R 13 ~R 17 and R 18 ~R 22 Adjacent groups in R can bond with each other to form a ring. 7 With R8 and R 17 With R 18 Rings can be formed by bonding together via single bonds, oxygen atoms, sulfur atoms, selenium atoms, or via nitrogen atoms. Additionally, R... 7 With R 8 and R 17 With R 18 In the case of forming a ring, it is preferable to form the ring by bonding with each other through single bonds, oxygen atoms, and sulfur atoms.
[0074] In general formula (1), in R 1 and R 2 It is a nitrile group, R 5 In the case of methoxy group, R 10 R 15 R 20 At least one of them is one of the above-mentioned groups other than methoxy.
[0075] In general formula (1), R is preferred. 1 and R 2 Each can be independently a nitrile group, a straight-chain or branched acyl group having 1 to 18 carbon atoms capable of having a substituent, or a straight-chain or branched alkoxycarbonyl group having 1 to 18 carbon atoms capable of having a substituent. Additionally, R can be... 1 and R 2 All are nitrile groups. Additionally, R can also be made... 1 It is a nitrile group, R 2 It is a straight-chain or branched alkoxy carbonyl group with 1 to 18 carbon atoms capable of having substituents. Alternatively, R can be... 1 and R 2 It is a straight-chain or branched alkoxy carbonyl group with 1 to 18 carbon atoms capable of having substituents. Alternatively, R can be... 1 and R 2 It consists of straight-chain or branched acyl groups with 1 to 18 carbon atoms that can have substituents, which bond together to form a ring.
[0076] In general formula (1), R 3 ~R 22 Preferably, it is a hydrogen atom, a straight-chain or branched alkoxy group having 1 to 20 carbon atoms that can have a substituent, or an amino group having 1 to 20 carbon atoms that can have a substituent. Additionally, R... 5 R 10 R 15 and R 20 It can be a straight-chain or branched alkoxy group with 1 to 20 carbon atoms capable of having substituents; for example, it can be a methoxy group. Additionally, R can be... 5 and R 15For linear or branched alkoxy groups with 1 to 20 carbon atoms that can have substituents, R 10 and R 20 The amino group can be a 1-20 carbon atom group having a substituent, and this amino group can have a straight-chain or branched alkoxy group having 1-20 carbon atoms. Additionally, R can be... 5 R 10 R 15 and R 20 The amino group is an amino group with 1 to 20 carbon atoms that can have substituents, and this amino group can have a straight-chain or branched alkoxy group with 1 to 20 carbon atoms. Additionally, R... 7 With R 8 and R 17 With R 18 They can form rings by bonding with each other through single bonds, oxygen atoms, or sulfur atoms.
[0077] In general formula (1), X 1 and X 2 The preferred expression is represented by general formula (2).
[0078] In general formula (2), R 23 ~R 28 Each of the following can be independently represented: a hydrogen atom; a straight-chain or branched alkyl group having 1 to 20 carbon atoms that can have substituents; a straight-chain or branched alkenyl group having 2 to 20 carbon atoms that can have substituents; a straight-chain or branched alkynyl group having 2 to 20 carbon atoms that can have substituents; a cycloalkyl group having 3 to 10 carbon atoms that can have substituents; a straight-chain or branched alkoxy group having 1 to 20 carbon atoms that can have substituents; a cycloalkoxy group having 3 to 10 carbon atoms that can have substituents; a thio group having 1 to 18 carbon atoms that can have substituents; an amino group having 1 to 20 carbon atoms that can have substituents; an aromatic hydrocarbon group having 6 to 36 carbon atoms that can have substituents; or a heterocyclic group having 5 to 36 cyclic atoms that can have substituents.
[0079] In general formula (2), as R 23 ~R 28 The "linear or branched alkyl group having 1 to 20 carbon atoms" in the term "linear or branched alkyl group having 1 to 20 carbon atoms capable of having substituents" can be exemplified by those in general formula (1) consisting of R 3 ~R 22 The same group as "a straight-chain or branched alkyl group that can have 1 to 20 carbon atoms and have substituents".
[0080] In general formula (2), as R 23 ~R 28The "alkenyl group with 2 to 20 carbon atoms" in the phrase "a straight-chain or branched alkenyl group capable of having substituents" can be exemplified by those derived from R in general formula (1). 3 ~R 22 The same group as "a straight-chain or branched alkenyl group that can have 2 to 20 carbon atoms with substituents".
[0081] In general formula (2), as R 23 ~R 28 The phrase "a straight-chain or branched alkynyl group with 2 to 20 carbon atoms capable of having substituents" can be exemplified by the alkynyl group represented by R in general formula (1). 3 ~R 22 The same group as "a straight-chain or branched alkynyl group that can have 2 to 20 carbon atoms with substituents".
[0082] In general formula (2), as R 23 ~R 28 The "cycloalkyl group with 3 to 10 carbon atoms" in the phrase "cycloalkyl group capable of having substituents" can be exemplified by those represented by R in general formula (1). 3 ~R 22 The same group is referred to as "a cycloalkyl group that can have 3 to 10 carbon atoms that are capable of having substituents".
[0083] In general formula (2), as R 23 ~R 28 The phrase "a straight-chain or branched alkoxy group with 1 to 20 carbon atoms capable of having substituents" can be exemplified by R in general formula (1). 3 ~R 22 The same group as "a straight-chain or branched alkoxy group that can have 1 to 20 carbon atoms that are capable of having substituents".
[0084] In general formula (2), as R 23 ~R 28 The "cycloalkoxy group with 3 to 10 carbon atoms" in the expression "cycloalkoxy group capable of having substituents" can be listed as R in general formula (1). 3 ~R 22 The same group as "a cycloalkoxy group that can have 3 to 10 carbon atoms that are substituents".
[0085] In general formula (2), as R 23 ~R 28The "thiogroup with 1 to 18 carbon atoms" in the expression "thiogroup capable of having substituents" can be listed as R in general formula (1). 1 R 2 The same group as "thiogroup with 1 to 18 carbon atoms that can have substituents".
[0086] In general formula (2), as R 23 ~R 28 The "amino group with 1 to 20 carbon atoms" in the expression "amino group capable of having substituents" can be listed as R in general formula (1). 1 R 2 The same group as "an amino group that can have 1 to 20 carbon atoms that are substituents".
[0087] In general formula (2), as R 23 ~R 28 The "aromatic hydrocarbon group with 6 to 36 carbon atoms" in the expression "aromatic hydrocarbon group with 6 to 36 carbon atoms capable of having substituents" can be listed as R in general formula (1). 3 ~R 22 The same group is referred to as "an aromatic hydrocarbon group that can have 6 to 36 carbon atoms as a substituent".
[0088] In general formula (2), as R 23 ~R 28 The "heterocyclic group with 5 to 36 cyclic atoms" in the expression "a heterocyclic group capable of having substituents" can be listed as R in general formula (1). 3 ~R 22 The same group as "a heterocyclic group with 5 to 36 cyclic atoms capable of having substituents".
[0089] In general formula (2), as R 23 ~R 28The "substituent" in the following categories can be listed as "a straight-chain or branched alkyl group having 1 to 18 carbon atoms that can have a substituent", "a straight-chain or branched alkenyl group having 2 to 20 carbon atoms that can have a substituent", "a straight-chain or branched alkynyl group having 2 to 20 carbon atoms that can have a substituent", "a cycloalkyl group having 3 to 10 carbon atoms that can have a substituent", "an alkoxy group having 1 to 20 carbon atoms that can have a substituent", "a straight-chain or branched cycloalkoxy group having 3 to 10 carbon atoms that can have a substituent", "an acyl group having 1 to 20 carbon atoms that can have a substituent", "a thio group having 1 to 18 carbon atoms that can have a substituent", "an amino group having 1 to 20 carbon atoms that can have a substituent", "an aromatic hydrocarbon group having 6 to 36 carbon atoms that can have a substituent", or "a heterocyclic group having 5 to 36 cyclic atoms that can have a substituent", and can be exemplified by R in general formula (1). 1 R 2 The same group as the "substituent" in "a straight-chain or branched acyl group that can have 1 to 18 carbon atoms that can have a substituent" etc.
[0090] In general formula (2), R 23 With R 24 R 25 With R 26 and R 27 With R 28 They can form rings by bonding with each other through single bonds, oxygen atoms, sulfur atoms, selenium atoms, or through nitrogen atoms.
[0091] In general formula (2), Y 1 It represents an oxygen atom, a sulfur atom, or a selenium atom.
[0092] In general formula (2), m and n represent integers from 0 to 2. When m is 0, n is 1 to 2, and when n is 0, m is 1 to 2. Either m or n is 1 or more, excluding cases where both are 0. m is preferably 1. In addition, the central skeleton of general formula (1), i.e., the cyclopentathiophene part, can be bonded by either the phenyl group represented by general formula (2) or the heterocyclic group of the 5-membered ring.
[0093] In general formula (2), it is preferable that m is 1 and n is 0 or 1. In general formula (2), when m is 1 and n is 1, it is preferable that the central skeleton of general formula (1), i.e., the cyclopentadithiophene part, is bonded to the heterocyclic group of the 5-membered ring.
[0094] Specific examples of compounds represented by the above general formula (1) of the present invention are shown below, but the present invention is not limited to these compounds. Furthermore, the following example compounds omit some hydrogen atoms, carbon atoms, etc., to represent one example of possible isomers, and include all other isomers. Additionally, mixtures of two or more isomers may each exist.
[0095]
Chemical Formula 3
[0096]
[0097] [Chemical Formula 4]
[0098]
[0099] [Chemical Formula 5]
[0100]
[0101]
Chemical Formula 6
[0102]
[0103] [Chemical Formula 7]
[0104]
[0105] [Chemical Formula 8]
[0106]
[0107] [Chemical Formula 9]
[0108]
[0109]
Chemical Formula 10
[0110]
[0111]
Chemical Formula 11
[0112]
[0113]
Chemical Formula 12
[0114]
[0115]
Chemical Formula 13
[0116]
[0117]
Chemical Formula 14
[0118]
[0119]
Chemical Formula 15
[0120]
[0121] [Chemical Formula 16]
[0122]
[0123]
Chemical Formula 17
[0124]
[0125] The hole transport material for the photoelectric conversion element of the present invention, represented by general formula (1), can be synthesized using known methods.
[0126] For example, for compound (A-1) X 1 and X 2 The compound represented by m=1 and n=0 of general formula (2) can be synthesized by a Suzuki-Miyaura cross-coupling reaction of a dibromo compound represented by formula (3) with a borate compound represented by formulas (4) and (5) or a borate ester compound represented by formulas (6) and (7), followed by a Knoevenagel condensation reaction with a compound represented by formula (8).
[0127] [Chemical Formula 18]
[0128]
[0129] As a method for purifying the compounds represented by the above general formula (1) of the present invention, it can be carried out by column purification using column chromatography, adsorption purification using silica gel, activated carbon, activated clay, etc., recrystallization using solvents, crystallization, etc. Alternatively, it is effective to use compounds whose purity is improved by combining these methods. In addition, the identification of these compounds can be performed by nuclear magnetic resonance analysis (NMR).
[0130] The preferred embodiment of the photoelectric conversion element of the present invention will be described below.
[0131] The preferred photoelectric conversion element of the present invention is: such as Figure 1 As shown, it comprises a conductive support 1, a hole blocking layer 2, an electron transport layer 3, a photoelectric conversion layer 4, a hole transport layer 5, and a counter electrode 6; Figure 2 As shown, it comprises a conductive support 7, an electron transport layer 8, a photoelectric conversion layer 9, a hole transport layer 10, and a counter electrode 11, but is not limited thereto. Furthermore, as the photoelectric conversion element of the present invention, a perovskite-type photoelectric conversion element is preferred. In the present invention, the perovskite-type photoelectric conversion element is preferably: Figure 1The structure sequentially comprises a conductive support 1, a hole blocking layer 2, an electron transport layer 3, a photoelectric conversion layer (perovskite layer) 4, a hole transport layer 5, and a counter electrode 6; Figure 2 The device comprises, in sequence, a conductive support 7, an electron transport layer 8, a photoelectric conversion layer (perovskite layer) 9, a hole transport layer 10, and a counter electrode 11, but may also omit the electron transport layer. Alternatively, it may be configured in the order of conductive support, hole transport layer, photoelectric conversion layer (perovskite layer), electron transport layer, and counter electrode.
[0132] <Conductive support>
[0133] In this invention, the conductive support needs to have light transmittance that allows light to pass through, which facilitates photoelectric conversion. Furthermore, the conductive support is a component that functions to extract current from the photoelectric conversion layer, and therefore a conductive substrate is preferred. Specific examples of conductive materials include conductive transparent oxide semiconductors such as tin-doped indium oxide (ITO), fluorine-doped tin oxide (FTO), and indium-tin composite oxides, but glass substrates coated with tin-doped indium oxide (ITO) or fluorine-doped tin oxide (FTO) films are preferred.
[0134] <Cavity Blocking Layer>
[0135] In the photoelectric conversion element of the present invention, it is preferable to have Figure 1 A hole-blocking layer 2 is formed on the conductive support 1 shown above. Specific examples of semiconductors used as the hole-blocking layer include one or more of the following: titanium oxide (TiO2, etc.), tungsten oxide (WO2, WO3, W2O3, etc.), zinc oxide (ZnO), niobium oxide (Nb2O5, etc.), tantalum oxide (Ta2O5, etc.), yttrium oxide (Y2O3, etc.), strontium titanate (SrTiO3, etc.), fullerene derivatives, and carbon nanotubes. In this invention, titanium oxide is preferred.
[0136] There is no particular limitation on the thickness of the hole blocking layer. From the viewpoint of further preventing the photoelectric conversion layer from coming into contact with the above-mentioned conductive support and causing a short circuit, it is preferably about 5nm to 100nm, and more preferably about 30nm to 90nm.
[0137] Hole-blocking layers can be obtained using known film-forming methods based on the material being formed. Examples of methods for fabricating hole-blocking layers include: spin coating of a dispersion containing semiconductor particles; spray pyrolysis of a semiconductor precursor solution by spraying it onto a conductive support placed on a heated plate using a sprayer; reaction by vaporizing the precursor; and ALD (Alternating Deposition) methods, but are not limited to these. In this invention, commercially available products can be used as the dispersion containing semiconductor particles.
[0138] When using a dispersion containing commercially available semiconductor particles, it is possible to reproduce high-efficiency perovskite solar cells by preventing the aggregation of semiconductor particles due to moisture in the environment. From this point of view, a dry environment is preferred.
[0139] <Electron transport layer>
[0140] In the photoelectric conversion element of the present invention, it is preferred that: Figure 1 An electron transport layer 3 is formed on the hole blocking layer 2 shown above; in addition, in Figure 2 In this process, an electron transport layer 8 is formed on the conductive support 7. The method is not particularly limited, however, in... Figure 1 In the case of a structure, a thin film with a porous structure is preferred. By having a porous structure, the active surface area of the photoelectric conversion layer is significantly increased, thereby improving the photoelectric conversion efficiency and enabling the fabrication of an electron transport layer with excellent electron collection capabilities. The electron transport layer is used to improve the efficiency of electron movement from the photoelectric conversion layer to the electrode and to block the movement of holes.
[0141] Specific examples of semiconductors forming the electron transport layer include: metal oxides such as tin oxide (SnO, SnO2, SnO3, etc.), titanium oxide (TiO2, etc.), tungsten oxide (WO2, WO3, W2O3, etc.), zinc oxide (ZnO), niobium oxide (Nb2O5, etc.), tantalum oxide (Ta2O5, etc.), yttrium oxide (Y2O3, etc.), and strontium titanate (SrTiO3, etc.); metal sulfides such as titanium sulfide, zinc sulfide, zirconium sulfide, copper sulfide, tin sulfide, indium sulfide, tungsten sulfide, cadmium sulfide, and silver sulfide; metal selenides such as titanium selenide, zirconium selenide, indium selenide, and tungsten selenide; and monomeric semiconductors such as silicon and germanium. It is preferable to use one or more of these semiconductors. In this invention, it is preferable to use one or more semiconductors selected from titanium oxide, zinc oxide, and tin oxide.
[0142] The electron transport layer can be obtained using known film-forming methods, depending on the material being formed. Examples of methods for forming the electron transport layer include: wet coating methods such as spin coating, blade coating, squeegee coating, and screen printing of a paste containing semiconductor microparticles onto a conductive substrate, followed by firing to remove solvents and additives; sputtering; vapor deposition; electrodeposition; electrolysis; and microwave irradiation, but these are not limited to these methods. The film-forming environment is not particularly restricted and can be atmospheric.
[0143] The thickness of the electron transport layer is not particularly limited, but from the viewpoint of being able to further collect electrons from the photoelectric conversion layer, it is preferably about 10 nm to 500 nm, more preferably about 50 nm to 400 nm. The semiconductor particle size is preferably 5 nm to 500 nm, more preferably 10 nm to 100 nm.
[0144] In this invention, the ointment containing semiconductor microparticles can be a commercially available product, or an ointment prepared by dispersing commercially available semiconductor microparticles in a solvent. Specific examples of solvents used in preparing the ointment include: water; alcohol-based solvents such as methanol, ethanol, and isopropanol; ketone-based solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; and hydrocarbon-based solvents such as n-hexane, cyclohexane, benzene, and toluene, but are not limited to these solvents. Furthermore, these solvents can be used as one or more mixed solvents.
[0145] As a method for dispersing semiconductor micropowder in a solvent in this invention, the powder can be ground using a mortar and pestle, or a disperser such as a ball mill, paint conditioner, vertical bead mill, horizontal bead mill, or ultrafine mill can be used. When preparing the paste, surfactants are preferably added to prevent the agglomeration of semiconductor particles, and thickeners such as polyethylene glycol are preferably added to increase its viscosity.
[0146] <Photoconversion layer>
[0147] In the photoelectric conversion element of the present invention, it is preferred that: Figure 1 A photoelectric conversion layer 4 is formed on the electron transport layer 3 shown; Figure 2 In this process, a photoelectric conversion layer 9 is formed on the electron transport layer 8, but it is not limited to this.
[0148] In this invention, when used as a perovskite-type photoelectric conversion element, the perovskite material serving as the photoelectric conversion layer refers to a series of materials having a structure represented by the general formula ABX3. Here, A, B, and X represent organic cations or monovalent metal cations, metal cations, and halide anions, respectively. As examples, A = K + 、Rb + Cs + CH3NH3 + (Hereinafter, MA: methylammonium), NH=CHNH2 + (Hereinafter, FA: formamidinium), CH3CH2NH3 + (Hereinafter, EA: ethylammonium); B = Pb, Sn; X = I - ,Br -Specifically, the following ingredients can be used: CH3NH3PbI3 (MAPBI3), C2H5NH3PbI3, CH3NH3PbBr3, C2H5NH3PbBr3, CH3NH3PbBr3, C2H5NH3PbCl3, CH3NH3PbCl3, C2H5NH3PbCl3, CsSnI3, CH3NH3SnI3, C2H5NH3SnI3, CsSnBr3, CH3NH3SnB The perovskite materials with any composition such as r3, C2H5NH3SnBr3, CsSnCl3, CH3NH3SnCl3, C2H5NH3SnCl3, etc., and layers of mixed cations and mixed anions of perovskite materials with any composition such as (FAMA)Pb(IBr)3, K(FAMA)Pb(IBr)3, Rb(FAMA)Pb(IBr)3, Cs(FAMA)Pb(IBr)3, etc., are not limited to these. Preferably, one or more of these perovskite materials are used. Additionally, light absorbers other than perovskite materials may be included.
[0149] The photoelectric conversion layer can be obtained using known film-forming methods such as the anti-solvent method or the two-stage method. In this invention, the anti-solvent method is preferred, but it is not a limitation.
[0150] In this invention, when using an antisolvent method to prepare a perovskite precursor solution as a photoelectric conversion layer, a specific solvent is added during the spin-coating process of this solution onto the electron transport layer. The photoelectric conversion layer is then obtained by heating after spin-coating.
[0151] Perovskite precursors can be commercially available materials, and in this invention, in... Figure 1 In the component configuration, a PbI2 / MAI(1:1)-DMF complex (Tokyo Chemicals) is preferably used. Figure 2 In the component configuration, precursors consisting of lead halides, methylammonium halides, formamidinium halides, and cesium halides are preferably used in any combination, but are not limited to this. It should be noted that MAI is an abbreviation for methylammonium iodide, and DMF is an abbreviation for N,N-dimethylformamide.
[0152] In this invention, from the viewpoint of the solubility of the perovskite precursor solution, solvents such as dimethyl sulfoxide, dimethylformamide, and γ-butyrolactone can be used as examples, but are not limited to these. Furthermore, one or more of these solvents can be used, with DMF and dimethyl sulfoxide being preferred.
[0153] The specific solvent added during spin coating of the perovskite precursor solution is preferably a poor solvent, and examples include: aromatic organic solvents such as toluene, benzene, chlorobenzene, o-dichlorobenzene, and nitrobenzene; ether solvents such as diethyl ether and tetrahydrofuran (THF); alcohol solvents such as methanol, ethanol, isopropanol, butanol, and octanol; long-chain hydrocarbon solvents such as hexane; pyridine; acetonitrile, etc., but not limited to these. One or more of these solvents may be used. Among them, aromatic organic solvents are preferred, and chlorobenzene and toluene are more preferred. The amount added is not particularly limited as long as it can sufficiently diffuse to the entire component substrate consisting of a conductive support, a hole blocking layer, and an electron transport layer that is rotated by spin coating.
[0154] In this invention, from the viewpoint of generating perovskite material from a precursor, the temperature at which the photoelectric conversion layer (perovskite layer) is heated by a hot plate or the like is preferably 50°C to 150°C, more preferably 70°C to 120°C. Furthermore, the heating time is preferably about 10 minutes to 90 minutes, more preferably about 30 minutes to 60 minutes.
[0155] From the viewpoint of reproducing high-efficiency perovskite solar cells by preventing the introduction of moisture, the environment during the film formation of perovskite materials is preferably a dry environment, more preferably a dry inert gas environment such as a glove box. Furthermore, it is preferable to use a solvent with low moisture content obtained by dehydration using molecular sieves or the like.
[0156] From the viewpoint of further suppressing defects and performance degradation caused by peeling, the thickness of the photoelectric conversion layer (perovskite layer) of the present invention is preferably 50 nm to 1000 nm, more preferably 200 nm to 700 nm.
[0157] Hole transport layer
[0158] A hole transport layer is a layer that functions to transport holes. Materials such as conductors, semiconductors, and organic hole transport materials can be used in the hole transport layer. This material functions as a hole transport material that receives and transports holes from the photoelectric conversion layer (perovskite layer). In this embodiment, high efficiency is achieved even without dopants as additives, but dopants may be included to further improve hole transport characteristics. Since there are concerns that dopants may reduce the durability of the photoelectric conversion element and shorten the overall lifespan of the element, it is desirable to reduce the amount used.
[0159] The hole transport layer of the present invention is a layer containing a compound represented by the above general formula (1) as a hole transport material for a photoelectric conversion element. By using the compound represented by general formula (1) in the hole transport layer, a photoelectric conversion element and a solar cell with high durability can be constructed. In addition, by using the compound represented by general formula (1) in the hole transport layer, good photoelectric conversion efficiency can be achieved. Furthermore, by using the compound represented by general formula (1) in the hole transport layer, sufficient photoelectric conversion efficiency can be achieved even with reduced or no dopant, and current can be extracted efficiently. By reducing or no dopant, photoelectric conversion elements and solar cells can be constructed with simple processes and low cost. In the hole transport layer of the present invention, one or more compounds represented by the above general formula (1) can be used together, and it can also be used together with other hole transport materials not belonging to the present invention. Specific examples of other hole transport materials include: compound semiconductors containing monovalent copper such as CuI, CuInSe2, and CuS; and compounds containing metals other than copper such as GaP, NiO, CoO, FeO, Bi2O3, MoO2, and Cr2O3. Organic hole transport materials include: polythiophene derivatives such as poly-3-hexylthiophene (P3HT) and polyvinyldioxythiophene (PEDOT); fluorene derivatives such as 2,2',7,7'-tetra-(N,N-di-p-methoxyphenylamine)-9,9'-spirodifluorene (Spiro-OMeTAD); carbazole derivatives such as polyvinylcarbazole; triphenylamine derivatives such as poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA); diphenylamine derivatives; polysilane derivatives; and polyaniline derivatives. Dopants (oxidants) can be added to the hole transport layer as needed.
[0160] The present invention Figure 1 The hole transport layer 5 shown is preferably formed on the photoelectric conversion layer 4 (perovskite layer) by coating and drying. Figure 2 The hole transport layer 10 shown is preferably formed on the photoelectric conversion layer 9 (perovskite layer) by coating and drying. Specifically, methods for film formation include spin coating, screen printing, roller coating, dip coating, spray coating, doctor blade coating, rod coating, mold coating, and curtain coating. In this invention, spin coating is preferred. It should be noted that the conditions for spin coating can be appropriately set.
[0161] In this invention, the solvents used in film formation may include: aromatic organic solvents such as benzene, toluene, xylene, mesitylene, tetrahydronaphthalene (1,2,3,4-tetrahydronaphthalene), monochlorobenzene, o-dichlorobenzene, m-dichlorobenzene, p-dichlorobenzene, and nitrobenzene; halogenated alkyl organic solvents such as dichloromethane, chloroform, 1,2-dichloroethane, 1,1,2-trichloroethane, and dichloromethane; nitrile solvents such as benzonitrile and acetonitrile; ether solvents such as tetrahydrofuran, dioxane, diisopropyl ether, C-pentylmethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate and propylene glycol monomethyl ether acetate; and alcohol solvents such as methanol, isopropanol, n-butanol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, cyclohexanol, and 2-n-butoxyethanol. However, this invention is not limited to these examples. Furthermore, one or more of the above solvents can be used in combination, allowing the selection of the solvent based on the structure. Aromatic organic solvents and halogenated alkyl organic solvents are particularly preferred.
[0162] In this invention, there are no particular restrictions on the conditions for drying after coating the hole transport layer as described above, but it is ideal to do so to the extent that the solvent can be removed. It is preferable to use a hot plate or the like to heat the material at about 50°C to 120°C for about 10 to 60 minutes.
[0163] In this invention, from the viewpoint of further improving photoelectric conversion efficiency, the thickness of the hole transport layer is preferably around 10 nm to 500 nm.
[0164] From the viewpoint of reproducing high-efficiency perovskite solar cells by preventing the introduction of moisture, the environment for forming the hole transport layer is preferably a dry environment, more preferably a dry environment such as a glove box. Furthermore, it is preferable to use a solvent with low moisture content obtained by dehydration using molecular sieves or the like.
[0165] <additive>
[0166] In this invention, a composition comprising a hole transport material for a photoelectric conversion element and a dopant (or oxidant), an alkaline compound (or alkaline additive), etc., as an additive can be used in the hole transport layer. Including an additive in the hole transport layer and increasing the carrier concentration (doping) of the hole transport material for the photoelectric conversion element in the hole transport layer contributes to improving the conversion efficiency of the photoelectric conversion element. In this invention, when using a composition comprising a dopant and an alkaline additive in the hole transport layer, a composition comprising an additive in an amount of 0 to 3.5 equivalents relative to the hole transport material for the photoelectric conversion element is preferred.
[0167] In this invention, when a dopant is included for the purpose of further improving hole transport characteristics, specific examples of dopants include tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridine)cobalt(III)tris[bis(trifluoromethane)sulfonylimide](FK209), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), silver bis(trifluoromethanesulfonyl)imide, NOSbF6, SbCl5, SbF5, etc. In this invention, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) is preferred.
[0168] In this invention, when using a composition containing a dopant, it is preferable to use a composition containing a dopant in an amount of 0 to 2.0 equivalents relative to the hole transport material 1 for the photoelectric conversion element, and more preferably a composition containing a dopant in an amount of 0 to 0.5 equivalents.
[0169] Alternatively, a basic compound (basic additive) may be included as an additive to the hole transport layer. In this invention, specific examples of basic compounds include 4-tert-butylpyridine (TBP), 2-methylpyridine, and 2,6-dimethylpyridine. Basic compounds are mostly used in conjunction with dopants. In this invention, it is ideal to use them in conjunction with dopants.
[0170] In this invention, when using a composition containing an alkaline compound, it is preferable to use a composition containing an alkaline compound in an amount of 0 to 5 equivalents relative to the hole transport material 1 for the photoelectric conversion element, and more preferably a composition containing an amount of 0 to 3 equivalents of an alkaline compound.
[0171] <Counter electrode>
[0172] In this invention, Figure 1 The counter electrode 6 shown is formed on the hole transport layer 5 by being arranged opposite to the conductive support 1. Figure 2 In the component configuration, the hole transport layer 10 is similarly formed, thereby enabling charge exchange with the hole transport layer. In the photoelectric conversion element of the present invention, it is preferable to have a metal electrode as a counter electrode in the hole transport layer, but an electron blocking layer may also be added between the hole transport layer and the counter electrode.
[0173] Specifically, materials used for the counter electrode include metals such as platinum, titanium, stainless steel, aluminum, gold, silver, and nickel, or their alloys.
[0174] In this invention, the counter electrode is preferably made of a material formed by methods such as vapor deposition. Furthermore, there are no particular limitations on the film thickness of the counter electrode; for example, it is preferably around 50 nm to 150 nm.
[0175] In the photoelectric conversion element of the present invention, the conductive support body serves as the cathode, and the counter electrode serves as the anode. Sunlight, or similar light, preferably irradiates from the conductive support side. Upon irradiation by sunlight, the photoelectric conversion layer (perovskite layer) absorbs the light and becomes excited, generating electrons and holes. These electrons move towards the electrode via the electron transport layer, and the holes move towards the electrode via the hole transport layer, thereby allowing current to flow and enabling the element to function as a photoelectric conversion element.
[0176] When evaluating the performance (characteristics) of the photoelectric conversion element of the present invention, short-circuit current density, open-circuit voltage, fill factor, and photoelectric conversion efficiency are measured. Short-circuit current density represents the current density at which 1 cm of current flows between the two terminals when the output terminals are short-circuited. 2 The current and open-circuit voltage represent the voltage between the two terminals when the output terminals are open. Additionally, the fill factor is the maximum output (product of current and voltage) divided by the product of the short-circuit current density and the open-circuit voltage, and is primarily affected by internal resistance. The photoelectric conversion efficiency is calculated by dividing the maximum output (W) by the number of terminals per 1cm². 2 The value of light intensity (W) is obtained by multiplying it by 100 and expressing it as a percentage.
[0177] In this invention, the durability of the photoelectric conversion element is evaluated by the retention rate (%) of the photoelectric conversion efficiency over time in a dry environment. The dry environment is defined as a state where a desiccant such as silica gel is placed in a sealed container such as a desiccant, and the humidity is below 5% RH.
[0178] The photoelectric conversion element of the present invention can be applied to solar cells, various optical sensors, etc. The solar cell of the present invention is preferably a perovskite solar cell, which is obtained by means of a photoelectric conversion element comprising a hole transport layer for a photoelectric conversion element using a compound represented by the above general formula (1) as the hole transport material for the photoelectric conversion element as a unit, and modularizing the required number of units and setting up the prescribed electrical wiring.
[0179] The preferred embodiments have been described above, but the present invention is not limited thereto, and appropriate changes can be made without departing from the scope of the present invention.
[0180] Example
[0181] The present invention will now be specifically described with reference to the accompanying drawings and examples; however, the present invention is not limited to the following examples. It should be noted that the compounds obtained in the synthetic examples were identified through… 1 The 1H-NMR (1H-NMR (Nuclear Magnetic Resonance Device manufactured by NEC Corporation, JNM-ECZ400S / L1 type)) was performed.
[0182] [Synthetic Example 1] Synthesis of Compound (A-1)
[0183] 3,3'-dibromo-5,5'-bis(trimethylsilyl)-2,2'-bithiophene (10.0 g, TCI) was added to the reaction vessel, followed by argon purging. Dehydrated tetrahydrofuran (106 mL) was added, and the mixture was cooled to -78°C using a dry ice-acetone bath. A hexane solution of n-butyllithium (1.55 mol / L, 29.0 mL, Kanto Chemical) was added dropwise. The mixture was then heated to -30°C over 4 hours, and dimethylcarbamoyl chloride (1.2 mL, TCI) was added. After stirring at -30°C for 20 minutes, the temperature was slowly increased over 3 hours to 0°C. The mixture was then cooled to room temperature. Water (150 mL) was added, and the mixture was separated. The organic layer was washed with water (150 mL) and saturated brine (100 mL). The aqueous layer was extracted three times with chloroform (40 mL). The organic layer was dried with anhydrous magnesium sulfate, and the solvent was removed by distillation, thus yielding a red solid as a crude product. The crude product was purified by silica gel column chromatography (hexane / ethyl acetate = 97 / 3 (volume ratio)) to give a compound represented by the following formula (9) as a red solid (yield: 5.76 g, 80%).
[0184] The compound of formula (9) obtained as described above (3.5 g), tetrahydrofuran (hereinafter referred to as THF, 21 mL) was added to the reaction vessel and cooled to below 5°C in an ice bath. N-bromosuccinimide (4.9 g, manufactured by TCI) and N,N-dimethylformamide (hereinafter referred to as DMF, 7 mL) were added in several portions. After that, the mixture was brought to room temperature and stirred for 2 hours. After the reaction was completed, the reaction solution was added to a beaker containing water (400 mL). After stirring for 30 minutes, the solution was filtered. The resulting solid was dried under reduced pressure at 70°C to give the compound represented by formula (10) as a purple solid (yield: 3.53 g, yield: 97%).
[0185] [Chemical Formula 19]
[0186]
[0187] 4-Bromoanisole (10.60 g, TCI), diphenylamine (8.72 g, TCI), palladium acetate (0.015 g), sodium tert-butoxide (11.90 g, Kanto Chemical), tri-tert-butylphosphine (0.017 g, Kanto Chemical), and toluene (110 mL) were added to a reaction vessel and degassed under reduced pressure. The mixture was heated under reflux for 3 hours in an argon atmosphere. After the reaction was completed, the mixture was cooled and filtered by suction. The residue was washed with toluene (50 mL), and the filtrate was concentrated. The crude product was purified by amino silica gel column chromatography (toluene / hexane = 1 / 1 (volume ratio)) and recrystallized (toluene / methanol) to give the compound of formula (11) as a white solid (yield: 11.02 g, 78%).
[0188] The compound of formula (11) obtained above (10.50 g) and THF (71 mL) were added to the reaction vessel and cooled to below 5 °C. N-bromosuccinimide (14.30 g, manufactured by TCI) was added and stirred at below 5 °C for 2 hours. After the reaction was completed, the reaction solution was added to a beaker containing 300 mL of water. Toluene (100 mL) was added to the solution. The mixture was separated, and the aqueous layer was extracted twice with toluene (40 mL). The organic layer was dried with sodium sulfate and concentrated. The crude product was purified by silica gel column chromatography (toluene / hexane = 1:1 (volume ratio)) to obtain the compound of formula (12) below as a yellow oil (yield: 16.50 g, 100%).
[0189]
Chemical Formula 20
[0190]
[0191] The compound of formula (12) obtained above (16.40 g), 4,4'-dimethoxydiphenylamine (2.90 g, manufactured by TCI), tris(dibenzylacetone)dipalladium(0) (0.68 g, manufactured by Kanto Chemical), sodium tert-butoxide (3.67 g, manufactured by Kanto Chemical), 1,1'-bis(diphenylphosphino)ferrocene (0.56 g, manufactured by Kanto Chemical), and toluene (25 mL) were added to the reaction vessel and degassed under reduced pressure. The mixture was heated under reflux for 4 hours in an argon atmosphere. After the reaction was completed, the mixture was cooled to below 40 °C and filtered by suction. The residue was washed with toluene (50 mL), and the filtrate was concentrated. The crude product was purified by silica gel column chromatography (toluene / hexane = 1 / 1 (volume ratio)) to give the compound of formula (13) below as a yellow solid (yield: 2.76 g, yield: 38%).
[0192] The compound of formula (13) obtained above (10.0 g) and anhydrous THF (130 mL) were added to the reaction vessel and degassed under reduced pressure. The mixture was cooled to below -70°C in an acetone-dry ice bath under an argon atmosphere. A solution of n-butyllithium hexane (1.55 M, 17.0 mL, manufactured by Kanto Chemical Co., Ltd.) was added dropwise in small amounts. After the addition was complete, the mixture was stirred at below -70°C for 1 hour, and then triisopropyl borate (6.0 mL, manufactured by TCI Co., Ltd.) was added dropwise. After the addition was complete, the mixture was slowly heated to room temperature and stirred at room temperature for 1 hour. The reaction was stopped by adding water (55 mL). The reaction mixture was separated, and the aqueous layer was extracted twice with toluene (40 mL). The organic layer was dried with sodium sulfate and concentrated. The crude product was purified by silica gel column chromatography (toluene → THF) to obtain the compound represented by formula (14) as a yellow powder (yield: 5.75 g, 62%).
[0193]
Chemical Formula 21
[0194]
[0195] The compound of formula (10) (1.00 g), the compound of formula (14) (4.59 g), potassium carbonate (19.0 g, manufactured by Kanto Chemical Co., Ltd.), tetrakis(triphenylphosphine)palladium(0) (0.15 mg, manufactured by Kanto Chemical Co., Ltd.), and toluene (150 mL) were added to the reaction vessel and degassed. The mixture was then heated under reflux for 68 hours in an argon atmosphere. After the reaction was complete, the mixture was cooled to below 50°C and filtered through diatomaceous earth. The residue was washed with toluene (100 mL), and the filtrate was concentrated. The crude product was purified by silica gel column chromatography (toluene → toluene / acetone = 100 / 1 (volume ratio)). The product was purified again by silica gel column chromatography (toluene / acetone = 100 / 1 (volume ratio)) to obtain the compound represented by formula (15) as a blackish-green powder (yield: 1.34 g, yield: 40%).
[0196]
Chemical Formula 22
[0197]
[0198] The compound of formula (15) above (0.57 g), malononitrile (0.13 g, TCI), and THF (15 mL) were added to a reaction vessel and stirred under an argon atmosphere. An acetic acid-pyridine solution (1:1, v / v) (3.6 mL) was then added. The mixture was stirred under reflux for 6 hours. After the reaction was complete, water (30 mL) and toluene (20 mL) were added. The mixture was separated, and the aqueous layer was extracted twice with toluene (30 mL). The organic layer was dried over magnesium sulfate and then concentrated. The crude product was purified by column chromatography (toluene) to obtain the compound represented by formula (A-1) as a blackish-green powder (yield: 0.493 g, 83%).
[0199] 1 H-NMR (400MHz, DMSO-d6): δ (ppm) = 3.72 (12H), 3.73 (6H), 6.7-6.8 (8H), 6.89 (8H), 6.92 (8H), 7.00 (8H), 7.05 (4H), 7.23 (2H), 7.33 (4H).
[0200]
Chemical Formula 23
[0201]
[0202] [Synthetic Example 2] Synthesis of Compound (A-11)
[0203] 3,6-Dibromocarbazole (5.0 g, TCI), 1-chloro-4-fluorobenzene (7.83 g, TCI), cesium carbonate (19.5 g, Kanto Chemical), and DMF (15 mL) were added to a reaction vessel. The mixture was stirred at 130 °C for 38 hours under an argon atmosphere. After the reaction was complete, the reaction solution was transferred to a beaker containing saturated brine (250 mL). The mixture was filtered, and the filtrate was washed with water (50 mL) and methanol (10 mL). The crude product was purified by silica gel column chromatography (toluene) to obtain the compound shown in formula (16) as a white powder (yield: 6.04 g, 92%).
[0204]
Chemical Formula 24
[0205]
[0206] The compound of formula (16) above (5.0 g), 4,4'-dimethoxydiphenylamine (5.27 g, manufactured by TCI), palladium acetate (0.11 g, manufactured by Kanto Chemical), sodium tert-butoxide (5.19 g, manufactured by Kanto Chemical), tri-tert-butylphosphine (33% xylene solution) (0.67 g, manufactured by Kanto Chemical), and toluene (30 mL) were added to a reaction vessel and degassed under reduced pressure in an argon atmosphere. The mixture was heated under reflux for 4 hours. After the reaction was completed, the reaction solution was filtered through diatomaceous earth. The residue was washed with toluene (30 mL), and the filtrate was concentrated. The crude product was purified by silica gel column chromatography (toluene → toluene / acetone = 100 / 1 (volume ratio)) to obtain the compound of formula (17) below as a yellow powder (yield: 3.10 g, yield: 39%).
[0207] The compound of formula (17) obtained above (3.10 g), bis(pinacolyl)diboron (2.13 g, manufactured by TCI), potassium acetate (2.06 g, manufactured by Kanto Chemical), 1,1'-bis(diphenylphosphino)ferrocene dichloropalladium (0.343 g, manufactured by Kanto Chemical), and 1,4-dioxane (27 mL) were added to the reaction vessel and degassed under reduced pressure in an argon atmosphere. The mixture was heated under reflux for 37 hours. After the reaction was completed, it was cooled to below 40°C and filtered through diatomaceous earth. The filtrate was concentrated, and the crude product was purified by silica gel column chromatography (toluene / acetone = 200 / 1 (volume ratio)). The product was purified again by silica gel column chromatography (toluene) to obtain the compound of formula (18) as a yellow powder (yield: 2.56 g, 74%).
[0208] [Chemical Formula 25]
[0209]
[0210] The compound of formula (10) (0.43 g), the compound of formula (18) (2.56 g), tetrakis(triphenylphosphine)palladium (0) (0.058 g, manufactured by Kanto Chemical Co., Ltd.), potassium carbonate (0.44 g, manufactured by Kanto Chemical Co., Ltd.), toluene (7 mL), ethanol (2 mL), and water (2 mL) were added to the reaction vessel and degassed under reduced pressure. The mixture was heated under reflux for 7 hours in an argon atmosphere. After the reaction was completed, toluene (20 mL) and water (10 mL) were added. The mixture was separated into layers, and the aqueous layer was extracted twice with toluene (20 mL), and the organic layer was concentrated. The crude product was purified by silica gel column chromatography (toluene / acetone = 100 / 1 (volume ratio)) to obtain the compound of formula (19) as a blackish-blue powder (yield: 1.65 g, yield: 84%).
[0211]
Chemical Formula 26
[0212]
[0213] The compound of formula (19) above (0.56 g), malononitrile (0.09 g, TCI), and THF (15 mL) were added to a reaction vessel and stirred under an argon atmosphere. An acetic acid-pyridine (1:1) solution (2.6 mL) was added. The mixture was stirred under reflux for 16 hours. After the reaction was complete, water (30 mL) was added. The mixture was filtered and washed with water (30 mL) and methanol (20 mL). The crude product was recrystallized (chloroform / acetone) to give the compound represented by formula (A-11) as a green powder (yield: 0.52 g, 91%).
[0214] 1 H-NMR (400MHz, THF-d8): δ (ppm) = 3.68 (24H), 6.72 (16H), 6.91 (16H), 7.08 (4H), 7.3 (4H), 7.66 (8H), 7.76 (2H), 7.90 (4H).
[0215] [Chemical Formula 27]
[0216]
[0217] [Synthetic Example 3] Synthesis of Compound (A-12)
[0218] The compound of formula (10) (0.43 g), the compound of formula (20) (2.04 g), tetrakis(triphenylphosphine)palladium (0) (0.058 g, manufactured by Kanto Chemical Co., Ltd.), potassium carbonate (0.44 g, manufactured by Kanto Chemical Co., Ltd.), toluene (7 mL), ethanol (2 mL), and water (2 mL) were added to a reaction vessel and degassed under reduced pressure. The mixture was heated under reflux for 7 hours in an argon atmosphere. After the reaction was completed, toluene (20 mL) and water (10 mL) were added. The mixture was separated into layers, and the aqueous layer was extracted twice with toluene (20 mL), and the organic layer was concentrated. The crude product was purified by silica gel column chromatography (toluene) and silica gel column chromatography (toluene:hexane = 2 / 1 (volume ratio)) to obtain the compound of formula (21) as a blackish-purple powder (yield: 1.42 g, yield: 86%).
[0219] [Chemical Formula 28]
[0220]
[0221] The compound of formula (21) above (0.60 g), malononitrile (0.12 g, TCI), and THF (19 mL) were added to a reaction vessel and stirred under an argon atmosphere. An acetic acid-pyridine (1:1) solution (3.2 mL) was added. The mixture was stirred under reflux for 54 hours. After the reaction was complete, the reaction solution was added to water (200 mL). The mixture was filtered and washed with water (30 mL) and methanol (20 mL). The crude product was washed with toluene and recrystallized (chloroform / acetone) to obtain the compound shown in formula (A-12) as a green powder (yield: 0.30 g, 48%).
[0222] 1 H-NMR (400MHz, THF-d8): δ (ppm) = 6.84 (8H), 7.00 (16H), 7.13 (16H), 7.19 (4H), 7.39 (4H), 7.55 (2H), 7.68 (4H), 7.86 (4H), 7.93 (4H).
[0223] [Chemical Formula 29]
[0224]
[0225] [Synthetic Example 4] Synthesis of Compound (A-26)
[0226] The compound of formula (10) (0.43 g), the compound of formula (22) (2.52 g), tetrakis(triphenylphosphine)palladium (0) (0.058 g, manufactured by Kanto Chemical Co., Ltd.), potassium carbonate (0.44 g, manufactured by Kanto Chemical Co., Ltd.), toluene (7 mL), ethanol (2 mL), and water (2 mL) were added to a reaction vessel and degassed under reduced pressure. The mixture was heated under reflux for 7 hours in an argon atmosphere. After the reaction was completed, toluene (20 mL) and water (10 mL) were added. The mixture was separated into layers, and the aqueous layer was extracted twice with toluene (20 mL), and the organic layer was concentrated. The crude product was purified by silica gel column chromatography (toluene / ethyl acetate = 50 / 1 (volume ratio)) to obtain the compound represented by formula (23) as a black powder (yield: 1.52 g, yield: 75%).
[0227]
Chemical Formula 30
[0228]
[0229] The compound of formula (23) above (0.56 g), malononitrile (0.09 g, TCI), and THF (15 mL) were added to a reaction vessel and stirred under an argon atmosphere. An acetic acid-pyridine (1:1) solution (2.6 mL) was added. The mixture was stirred under reflux for 16 hours. After the reaction was complete, water (30 mL) was added. The mixture was filtered and washed with water (30 mL) and methanol (20 mL). The crude product was recrystallized (chloroform / acetone) to give the compound represented by formula (A-26) as a green powder (yield: 0.51 g, 88%).
[0230] 1 H-NMR (400MHz, THF-d8): δ (ppm) = 3.67 (24H) 6.65 (16H), 6.84 (16H), 6.96 (4H), 7.11 (4H), 7.57 (8H), 7.59 (2H), 7.80 (4H).
[0231]
Chemical Formula 31
[0232]
[0233] [Synthetic Example 5] Synthesis of Compound (A-41)
[0234] The compound of formula (10) (0.43 g), the compound of formula (24) (2.48 g), tetrakis(triphenylphosphine)palladium (0) (0.058 g, manufactured by Kanto Chemical Co., Ltd.), potassium carbonate (0.44 g, manufactured by Kanto Chemical Co., Ltd.), toluene (7 mL), ethanol (2 mL), and water (2 mL) were added to a reaction vessel and degassed under reduced pressure. The mixture was heated under reflux for 7 hours in an argon atmosphere. After the reaction was completed, toluene (20 mL) and water (10 mL) were added. The mixture was separated into layers, and the aqueous layer was extracted twice with toluene (20 mL), and the organic layer was concentrated. The crude product was purified by silica gel column chromatography (toluene / ethyl acetate = 50 / 1 (volume ratio)) to obtain the compound of formula (25) as a black powder (yield: 1.52 g, yield: 77%).
[0235]
Chemical Formula 32
[0236]
[0237] The compound of formula (25) above (0.55 g), malononitrile (0.09 g, TCI), and THF (15 mL) were added to a reaction vessel and stirred under an argon atmosphere. An acetic acid-pyridine (1:1) solution (2.6 mL) was added. The mixture was stirred under reflux for 16 hours. After the reaction was complete, water (30 mL) was added. The mixture was filtered and washed with water (30 mL) and methanol (20 mL). The crude product was recrystallized (chloroform / acetone) to give the compound represented by formula (A-41) as a green powder (yield: 0.51 g, 90%).
[0238] 1 H-NMR (400MHz, THF-d8): δ (ppm) = 3.68 (24H), 6.68 (16H), 6.88 (16H), 7.00 (4H), 7.15 (4H), 7.62 (8H), 7.64 (2H), 7.85 (4H).
[0239]
Chemical Formula 33
[0240]
[0241] [Synthetic Example 6] Synthesis of Compound (A-56)
[0242] The compound of formula (10) above (0.88 g), [4-[bis(4-methoxyphenyl)amino]phenyl]boronic acid (2.10 g, TCI), tetra(triphenylphosphine)palladium (0) (0.12 g, Kanto Chemical), potassium carbonate (0.90 g, Kanto Chemical), toluene (13 mL), ethanol (4.5 mL), and water (4.5 mL) were added to the reaction vessel and degassed under reduced pressure. The mixture was heated under reflux for 6 hours in an argon atmosphere. After the reaction was completed, toluene (10 mL) and water (10 mL) were added. The mixture was separated, and the aqueous layer was extracted twice with toluene (20 mL). The organic layer was concentrated, and the crude product was purified by silica gel column chromatography (toluene / acetone = 100 / 1 (volume ratio)). The product was purified again by silica gel column chromatography (toluene) to obtain the compound of formula (26) below as a blackish-green powder (yield: 1.86 g, yield: 93%).
[0243]
Chemical Formula 34
[0244]
[0245] The compound of formula (26) (0.6 g), diethyl malonate (0.37 g, TCI), and THF (14 mL) were added to the reaction vessel and stirred under an argon atmosphere. The mixture was cooled to below 5°C in an ice bath, and carbon tetrachloride (0.9 mL, Pure Chemical Industries, Inc.), titanium tetrachloride (0.5 mL, Wako Pure Chemical Industries, Inc.), and THF (8 mL) were added. The mixture was cooled again to below 5°C, and pyridine (1 mL) and THF (1 mL) were added. The mixture was then heated to room temperature and stirred for 17 hours. After the reaction was complete, the reaction solution was added to a beaker containing 50 mL of water, and toluene (30 mL) was added. The mixture was separated, and the organic layer was washed twice with a 10% sodium carbonate aqueous solution (50 mL). The organic layer was dried with magnesium sulfate and then concentrated. The crude product was purified by silica gel column chromatography (toluene) to give the compound represented by the following formula (A-56) as a blackish-green powder (yield: 0.56 g, 79%).
[0246] 1 H-NMR (400MHz, CDCl3): δ (ppm) = 1.38 (6H), 3.81 (12H), 4.40 (4H), 6.84 (8H), 6.90 (4H), 7.07 (8H), 7.31 (4H), 7.36 (2H).
[0247]
Chemical Formula 35
[0248]
[0249] [Synthetic Example 7] Synthesis of Compound (A-58)
[0250] The following compounds were added to a reaction vessel: 1.33 g of the compound of formula (27), 2.10 g of [4-[bis(4-methoxyphenyl)amino]phenyl]boronic acid (TCI), 0.12 g of tetra(triphenylphosphine)palladium (0), 0.90 g of potassium carbonate (Kanto Chemical), 13 mL of toluene, 4.5 mL of ethanol, and 4.5 mL of water. The mixture was degassed under reduced pressure. The mixture was heated under reflux for 6 hours at an argon atmosphere. After the reaction was complete, 10 mL of toluene and 10 mL of water were added. The mixture was separated, and the aqueous layer was extracted twice with 20 mL of toluene. The organic layer was concentrated, and the crude product was purified by silica gel column chromatography (toluene) to obtain the compound represented by formula (A-58) as a blackish-green powder (yield: 2.11 g, 86%).
[0251] 1H-NMR (400MHz, CDCl3): δ (ppm) = 1.32 (6H), 3.81 (12H), 4.59 (4H), 6.84 (8H), 6.90 (4H), 7.08 (8H), 7.33 (4H), 7.69 (2H).
[0252]
Chemical Formula 36
[0253]
[0254] [Synthetic Example 8] Synthesis of Compound (A-63)
[0255] The compound of formula (26) (0.6 g), methyl cyanoacetate (0.23 g, TCI), and THF (14 mL) were added to the reaction vessel and stirred under an argon atmosphere. The mixture was cooled to below 5°C in an ice bath, and carbon tetrachloride (0.9 mL, Pure Chemical Industries, Inc.), titanium tetrachloride (0.5 mL, Washi Powder Chemical Co., Ltd.), and THF (8 mL) were added. The mixture was cooled again to below 5°C, and pyridine (1 mL) and THF (1 mL) were added. The mixture was then heated to room temperature and stirred for 18 hours at room temperature, followed by stirring at 60°C for 14 hours. After the reaction was complete, the reaction mixture was added to a beaker containing 50 mL of water, and toluene (30 mL) was added. The mixture was separated, and the organic layer was washed twice with a 10% sodium carbonate aqueous solution (50 mL). The organic layer was dried with magnesium sulfate and then concentrated. The crude product was purified by silica gel column chromatography (toluene) to give the compound represented by the following formula (A-63) as a blackish-green powder (yield: 0.51 g, 77%).
[0256] 1 H-NMR (400MHz, CDCl3): δ (ppm) = 3.81 (12H), 3.95 (3H), 6.84 (8H), 6.90 (4H), 7.07 (8H), 7.34 (4H), 7.68 (1H), 7.82 (1H).
[0257]
Chemical Formula 37
[0258]
[0259] [Synthetic Example 9] Synthesis of Compound (A-66)
[0260] The compound of formula (10) above (0.88 g), 4-(diphenylamino)phenylboronic acid (1.73 g, Sigma-Aldrich), tetra(triphenylphosphine)palladium(0) (0.12 g, Kanto Chemical), potassium carbonate (0.90 g, Kanto Chemical), toluene (13 mL), ethanol (4.5 mL), and water (4.5 mL) were added to a reaction vessel and degassed under reduced pressure. The mixture was heated under reflux for 13 hours in an argon atmosphere. After the reaction was completed, the reaction solution was added to a beaker containing ethanol (50 mL). The mixture was filtered, washed twice with water (50 mL), and washed with ethanol (20 mL). The crude product was purified by silica gel column chromatography (toluene → chloroform). The crystals were then dispersed and washed with toluene to obtain the compound represented by formula (28) as a blackish-blue powder (yield: 1.14 g, 67%).
[0261] [Chemical Formula 38]
[0262]
[0263] The compound of formula (28) above (0.60 g), malononitrile (0.23 g, TCI), and THF (50 mL) were added to a reaction vessel and stirred under an argon atmosphere. An acetic acid-pyridine (1:1) solution (5.6 mL) was added. The mixture was stirred under reflux for 32 hours. After the reaction was complete, the reaction solution was added to a beaker containing water (300 mL). The mixture was filtered and washed with water (20 mL) and methanol (20 mL). The crude product was dispersed and washed with acetone, and recrystallized (chloroform) to obtain the compound represented by formula (A-66) as a black powder (yield: 0.44 g, 69%).
[0264] 1 H-NMR (400MHz, THF-d8): δ (ppm) = 7.01 (8H), 7.06 (8H), 7.23 (8H), 7.45 (4H), 7.49 (2H).
[0265] [Chemical Formula 39]
[0266]
[0267] [Synthetic Example 10] Synthesis of Compound (A-98)
[0268] The compound of formula (10) (0.88 g), the compound of formula (29) (2.55 g), potassium carbonate (0.90 g, manufactured by Kanto Chemical Co., Ltd.), tetrakis(triphenylphosphine)palladium (0.12 g, manufactured by Kanto Chemical Co., Ltd.), toluene (13 mL), ethanol (4.5 mL), and water (4.5 mL) were added to a reaction vessel and heated under reflux for 6 hours. After the reaction was completed, the reaction solution was transferred to a beaker containing water (150 mL), and toluene (20 mL) was added. The mixture was then separated. The organic layer was dried with magnesium sulfate and concentrated. The crude product was purified by silica gel column chromatography (toluene) to obtain the compound of formula (30) as a blackish-blue powder (yield: 1.81 g, yield: 84%).
[0269]
Chemical Formula 40
[0270]
[0271] The compound (30) above (0.60 g), malononitrile (0.22 g, TCI), and THF (29 mL) were added to a reaction vessel and stirred under an argon atmosphere. A mixture of acetic acid and pyridine (volume ratio = 1:1) (5.0 mL) was added, and the mixture was heated under reflux for 21 hours. After the reaction was completed, the reaction solution was transferred to a beaker containing water (150 mL). The solution was filtered, and the solid was washed with water (20 mL) and methanol (20 mL). The crude product was purified by silica gel column chromatography (toluene) and recrystallized (chloroform: acetone) to give the compound represented by the following formula (A-98) as a black solid (yield: 0.54 g, yield: 84%).
[0272] 1 H-NMR (400MHz, CDCl3): δ (ppm) = 2.48 (2H), 7.02-7.06 (12H), 7.18-7.21 (8H), 7.38 (4H), 7.45 (2H).
[0273]
Chemical Formula 41
[0274]
[0275] [Synthetic Example 11] Synthesis of Compound (A-114)
[0276] The following compounds (31) were added to a reaction vessel: 0.32 g of compound (31), 0.49 g of [4-[bis(4-methoxyphenyl)amino]phenyl]boronic acid (TCI), 0.03 g of tetra(triphenylphosphine)palladium (0), 0.22 g of potassium carbonate (Kanto Chemical), 4 mL of toluene, 1.3 mL of ethanol, and 1.3 mL of water. The mixture was degassed under reduced pressure. The mixture was stirred under reflux for 6 hours in an argon atmosphere. After the reaction was complete, the reaction mixture was added to 100 mL of water. 20 mL of toluene was added to the mixture, and the layers were separated. The organic layer was dried with magnesium sulfate and then concentrated. The crude product was purified by silica gel column chromatography (toluene) to obtain the compound represented by the following formula (32) as a blackish-green powder (yield: 0.40 g, 69%).
[0277]
Chemical Formula 42
[0278]
[0279] The compound of formula (32) above (0.35 g), diethyl malonate (0.27 mL, TCI), and THF (11 mL) were added to a reaction vessel and stirred under an argon atmosphere. Pyridine (0.48 mL, Nakalai Tesque) was then added, followed by titanium tetrachloride (0.24 mL, Wasshoku Pure Chemicals), and the mixture was stirred at room temperature for 9 hours. After the reaction was complete, the reaction solution was transferred to a beaker containing water (150 mL). The solution was filtered, washed with water (30 mL) and methanol (20 mL), and dried. The crude product was purified by silica gel column chromatography (toluene / ethyl acetate = 50 / 1 (v / v)) to obtain the compound represented by formula (A-114) as a blackish-green powder (yield: 0.32 g, 82%).
[0280] 1 H-NMR (400MHz, THF-d8): δ (ppm) = 1.35 (6H), 3.73 (12H), 4.39 (4H), 6.81-6.88 (12H), 7.02 (8H), 7.12 (2H), 7.15 (2H), 7.39-7.42 (6H).
[0281]
Chemical Formula 43
[0282]
[0283] [Synthetic Example 12] Synthesis of Compound (A-115)
[0284] The compound of formula (31) (0.32 g), the compound of formula (33) (1.15 g), tetrakis(triphenylphosphine)palladium (0) (0.03 g, manufactured by Kanto Chemical Co., Ltd.), potassium carbonate (0.22 g, manufactured by Kanto Chemical Co., Ltd.), toluene (4 mL), ethanol (1.3 mL), and water (1.3 mL) were added to a reaction vessel and degassed under reduced pressure. The mixture was stirred under reflux for 6 hours in an argon atmosphere. After the reaction was completed, the reaction solution was added to water (100 mL). Toluene (20 mL) was added to the solution, and the mixture was separated. The organic layer was dried with magnesium sulfate and then concentrated. The crude product was purified by silica gel column chromatography (toluene / ethyl acetate = 40 / 1 (volume ratio)) to obtain the compound represented by formula (34) as a blackish-green powder (yield: 0.64 g, yield: 61%).
[0285]
Chemical Formula 44
[0286]
[0287] The compound of formula (34) (0.32 g), malononitrile (0.05 g, TCI), and THF (8 mL) were added to a reaction vessel and stirred under an argon atmosphere. A mixture of acetic acid and pyridine (volume ratio = 1:1) (1.4 mL) was added, and the mixture was heated under reflux for 20 hours. After the reaction was complete, the reaction solution was added to a beaker containing 150 mL of water. The mixture was filtered, washed with 20 mL of water and 20 mL of methanol, and dried. The crude product was purified by silica gel column chromatography (toluene / ethyl acetate = 40 / 1 (volume ratio)) to obtain the compound represented by formula (A-115) as a blackish-green powder (yield: 0.26 g, 81%).
[0288] 1 H-NMR (400MHz, THF-d8): δ (ppm) = 3.67 (24H), 6.69-6.71 (16H), 6.88-6.90 ( 16H), 7.07(4H), 7.28-7.31(6H), 7.47(4H), 7.61(4H), 7.64(4H), 7.89(4H).
[0289] [Chemical Formula 45]
[0290]
[0291] [Example 1] Fabrication of photoelectric conversion element and evaluation of photoelectric conversion characteristics
[0292] The glass substrate (conductive support 1, manufactured by Solaronix) that has been etched and coated with a fluorine-doped tin oxide (FTO) film was ultrasonically cleaned with acetone and then subjected to UV ozone treatment.
[0293] A titanium dioxide (TiO2) solution (Ti-Nanoxide BL / SC, manufactured by Solaronix) for a hole-blocking layer was coated onto the substrate using spin coating. After coating, the film was calcined at 500°C for 1 hour to obtain a TiO2 film with a thickness of 50 nm to 70 nm (hole-blocking layer 2). Next, a titanium dioxide (TiO2) dispersion for an electron transport layer, prepared by a titanium dioxide (TiO2) paste (PST-18NR, manufactured by Nichibukai Chemical Co., Ltd.):ethanol = 1:4 (weight ratio), was coated onto the substrate using spin coating. After coating, the film was calcined at 450°C for 30 minutes to obtain a mesoporous titanium dioxide (TiO2) film with a thickness of 330 nm (electron transport layer 3).
[0294] Next, a 1.5 M solution was prepared by dissolving the PbI2 / MAI(1:1)-DMF composite (manufactured by Tokyo Chemical Co., Ltd.) in dimethyl sulfoxide. The prepared dimethyl sulfoxide solution was spin-coated onto a mesoporous titanium dioxide (TiO2) film at room temperature. During the spin-coating process, 0.3 mL of chlorobenzene was added dropwise to form a film. The film was then dried at 110 °C for 1 hour using a hot plate to form a CH3NH3PbI3 layer (photoelectric conversion layer 4) with a thickness of approximately 500 nm.
[0295] Next, a chlorobenzene solution containing 75 mM of 4-tert-butylpyridine as an additive and 12.5 mM of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, 0.5 equivalent) as a dopant was prepared as a doping solution. Using the prepared doping solution and the compound (A-1) obtained in Synthesis Example 1 as a hole transport material for photoelectric conversion elements, a 50 mM chlorobenzene solution was prepared as a hole transport layer solution. The hole transport layer solution was spin-coated onto a CH3NH3PbI3 layer (photoelectric conversion layer 4) at room temperature and dried at 70°C for 30 minutes using a hot plate to form a hole transport layer 5 with a thickness of approximately 300 nm.
[0296] Vacuum evaporation was used on hole transport layer 5 at a vacuum degree of 1×10⁻⁶. -4 Gold is filmed at a thickness of 80nm to 100nm at approximately 100nm, and a gold electrode (counter electrode 6) is set therefrom to fabricate a photoelectric conversion element.
[0297] Light generated by a simulated sunlight irradiation device (OTENTO-SUN III type, manufactured by Spectrometer Co., Ltd.) was irradiated onto the transparent electrode side of the aforementioned photoelectric conversion element. The current-voltage characteristics were measured using a SourceMeter (KEITHLEY, Model 2400 General-Purpose SourceMeter). The light intensity was adjusted to 100 mW / cm². 2 Measurements were performed. The initial photoelectric conversion efficiency was obtained from the measured current-voltage characteristics. Furthermore, the photoelectric conversion element was stored in a desiccator equipped with silica gel for 168 hours from the initial photoelectric conversion efficiency measurement, and the photoelectric conversion efficiency after storage (photoelectric conversion efficiency over time) was evaluated. Additionally, as an evaluation of durability, the retention rate (%) of the photoelectric conversion efficiency after 168 hours of storage from the initial photoelectric conversion efficiency measurement was calculated according to the following formula (a-1). The calculated retention rate (%) is shown in Table 2.
[0298]
Mathematical Formula 1
[0299]
[0300] [Example 2]
[0301] Using the compound (A-11) obtained in Synthesis Example 2 as a hole transport material for the photoelectric conversion element, a 50 mM chlorobenzene solution was prepared and used as the hole transport layer solution. Except for using this compound (A-11) and without using lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as a dopant and 4-tert-butylpyridine (0 mM) as an additive, the photoelectric conversion element was fabricated in the same manner as in Example 1, and its current-voltage characteristics were measured to obtain the initial photoelectric conversion efficiency. Furthermore, the photoelectric conversion efficiency (time-dependent photoelectric conversion efficiency) of the photoelectric conversion element obtained in Example 2 was obtained after 168 hours of storage in a desiccator equipped with silica gel from the initial photoelectric conversion efficiency measurement. Table 1 shows the ratio of the photoelectric conversion efficiency of Example 2 after 168 hours of storage to the photoelectric conversion efficiency of Comparative Example 1 after 168 hours of storage (based on the same conditions as Example 2) (hereinafter referred to as "ratio to Comparative Example 1"). Table 2 shows the retention rate (%) of the photoelectric conversion efficiency after 168 hours of storage from the initial conversion efficiency measurement in the form of an evaluation of the durability of the photoelectric conversion element of Example 2. Here, the ratio to Comparative Example 1 shown in Table 1 represents the value obtained by dividing the photoelectric conversion efficiency of Example 2 after 168 hours of storage (photoelectric conversion efficiency over time) by the photoelectric conversion efficiency of Comparative Example 1 after 168 hours of storage (photoelectric conversion efficiency over time).
[0302] [Example 3]
[0303] Except for the use of compound (A-11), the photoelectric conversion element was fabricated in the same manner as in Example 1, and the current-voltage characteristics were measured to obtain the initial photoelectric conversion efficiency and the photoelectric conversion efficiency after 168 hours of storage. Table 1 shows the ratio of the photoelectric conversion efficiency after 168 hours of storage from the initial photoelectric conversion efficiency measurement to that of Comparative Example 1, and Table 2 shows the retention rate (%) of the photoelectric conversion efficiency after 168 hours of storage from the initial conversion efficiency measurement as an evaluation of durability.
[0304] [Example 4]
[0305] Except for the use of compound (A-56), the photoelectric conversion element was fabricated in the same manner as in Example 2, and the current-voltage characteristics were measured to obtain the initial photoelectric conversion efficiency and the photoelectric conversion efficiency after 168 hours of storage. Table 1 shows the ratio of the photoelectric conversion efficiency after 168 hours of storage from the initial photoelectric conversion efficiency measurement to that of Comparative Example 1, and Table 2 shows the retention rate (%) of the photoelectric conversion efficiency after 168 hours of storage from the initial conversion efficiency measurement as an evaluation of durability.
[0306] [Example 5]
[0307] Except for the use of compound (A-56), the photoelectric conversion element was fabricated in the same manner as in Example 1, and the current-voltage characteristics were measured to obtain the initial photoelectric conversion efficiency and the photoelectric conversion efficiency after 168 hours of storage. Table 1 shows the ratio of the photoelectric conversion efficiency after 168 hours of storage from the initial photoelectric conversion efficiency measurement to that of Comparative Example 1, and Table 2 shows the retention rate (%) of the photoelectric conversion efficiency after 168 hours of storage from the initial conversion efficiency measurement as an evaluation of durability.
[0308] [Example 6]
[0309] Except for the use of compound (A-63), the photoelectric conversion element was fabricated in the same manner as in Example 2, and the current-voltage characteristics were measured to obtain the initial photoelectric conversion efficiency and the photoelectric conversion efficiency after 168 hours of storage. Table 1 shows the ratio of the photoelectric conversion efficiency after 168 hours of storage from the initial photoelectric conversion efficiency measurement to that of Comparative Example 1, and Table 2 shows the retention rate (%) of the photoelectric conversion efficiency after 168 hours of storage from the initial conversion efficiency measurement as an evaluation of durability.
[0310] [Example 7]
[0311] Except for the use of compound (A-63), the photoelectric conversion element was fabricated in the same manner as in Example 1, and the current-voltage characteristics were measured to obtain the initial photoelectric conversion efficiency and the photoelectric conversion efficiency after 168 hours of storage. Table 1 shows the ratio of the photoelectric conversion efficiency after 168 hours of storage from the initial photoelectric conversion efficiency measurement to that of Comparative Example 1.
[0312] [Comparative Example 1]
[0313] Except for using Spiro-OMeTAD (manufactured by Sigma-Aldrich), the standard hole transport material represented by the following formula (B-1), the photoelectric conversion element was fabricated in the same manner as in Example 1, and the current-voltage characteristics were measured to obtain the initial photoelectric conversion efficiency and the photoelectric conversion efficiency after 168 hours of storage. The initial photoelectric conversion efficiency was 6.03%. Table 2 shows the retention rate (%) of the photoelectric conversion efficiency after 168 hours of storage from the initial conversion efficiency measurement as an evaluation of durability.
[0314]
Chemical Formula 46
[0315]
[0316] Table 1
[0317]
[0318] Table 2
[0319]
[0320] As shown in Table 1, compounds (A-11) and (A-56) exhibit higher and more adequate photoelectric conversion efficiencies than the commonly used comparative examples. Furthermore, compound (A-63) shows photoelectric conversion efficiencies comparable to those of the commonly used comparative examples. This demonstrates that compounds (A-11), (A-56), and (A-63) can be used as hole transport layers in photoelectric conversion devices even with reduced or no dopant. Therefore, photoelectric conversion devices containing compounds (A-11), (A-56), or (A-63) can reduce manufacturing costs by lowering the doping amount, eliminating the need for doping operations, and can be fabricated with a simpler process and lower cost.
[0321] Furthermore, the results in Table 2 show that the photoelectric conversion element using a hole transport layer containing compound (A-1), compound (A-11), compound (A-56), or compound (A-63) exhibits high photoelectric conversion efficiency even after 168 hours, and its retention rate is superior to that of the compounds in the comparative examples.
[0322] [Example 8] Fabrication and Current-Voltage Characteristic Evaluation of Photoelectric Conversion Element
[0323] The glass with the FLAT ITO film (conductive support 7, manufactured by GEOMATEC) was ultrasonically cleaned with isopropanol and then subjected to UV ozone treatment.
[0324] A tin(IV) oxide (15% inH2O colloidal dispersion) (manufactured by Alfa Aesar) and purified water in a volume ratio of 1:9 was spin-coated onto the substrate (as a coating solution for the electron transport layer). The substrate was then heated at 150°C for 30 minutes using a hot plate, thereby forming an electron transport layer 8 with a thickness of approximately 20 nm.
[0325] In a glove box under a nitrogen atmosphere, formamidinium hydroiodate (1M, manufactured by Tokyo Chemical Co., Ltd.), lead(II) iodide (1.1M, manufactured by Tokyo Chemical Co., Ltd.), methylamine hydrobromide (0.2M, manufactured by Tokyo Chemical Co., Ltd.), and lead(II) bromide (0.2M, manufactured by Tokyo Chemical Co., Ltd.) were dissolved in a mixed solvent of dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1. A perovskite precursor solution was prepared by adding a dimethyl sulfoxide solution containing cesium iodide (1.5M, manufactured by Tokyo Chemical Co., Ltd.) to the solution, with the amount of cesium added being 5% of the composition.
[0326] In a glove box under a nitrogen atmosphere, the prepared perovskite precursor solution was dropwise and spin-coated onto a tin oxide film. During the spin-coating process, 0.3 mL of chlorobenzene was added dropwise to coat the perovskite precursor. Subsequently, the film was heated at 100 °C for 1 hour using a hot plate to form a Cs(MAFA)Pb(IBr)3 layer (photoelectric conversion layer 9) with a thickness of approximately 500 nm.
[0327] In a glove box under a nitrogen atmosphere, a chlorobenzene solution containing 150 mM 4-tert-butylpyridine and 25 mM lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, 0.5 equivalent) as a dopant was prepared. The compound (A-63) obtained in Synthesis Example 11 as a hole transport material was dissolved in this chlorobenzene solution at 50 mM at room temperature to prepare a coating solution for the hole transport layer.
[0328] In a glove box under a nitrogen atmosphere, a hole transport layer coating solution was spin-coated onto a Cs(MAFA)Pb(IBr)3 layer (photoelectric conversion layer 9) to form a hole transport layer 10 with a film thickness of approximately 200 nm.
[0329] Vacuum evaporation was used on the hole transport layer 10 at a vacuum degree of 1×10⁻⁶. -4Gold is deposited at a thickness of about 80 nm to form a gold electrode (counter electrode 11) and a photoelectric conversion element is fabricated.
[0330] The conductive support side of the aforementioned photoelectric conversion element is irradiated with an intensity of 100 mW / cm² generated by a simulated sunlight irradiation device (OTENTO-SUN III type manufactured by Spectrometer Co., Ltd.). 2 The light was measured using a SourceMeter (KEITHLEY, Model 2400 General-Purpose SourceMeter) to determine the current-voltage characteristics, thereby obtaining the initial photoelectric conversion efficiency. The photoelectric conversion element was stored in a desiccator equipped with silica gel for 30 days from the initial photoelectric conversion efficiency measurement, and the current-voltage characteristics were measured again to obtain the photoelectric conversion efficiency after 30 days (720 hours). Table 3 shows the ratio of the photoelectric conversion efficiency of the photoelectric conversion element of Example 8 after 720 hours of storage (as the photoelectric conversion over time) from the initial photoelectric conversion efficiency measurement to the photoelectric conversion efficiency of the photoelectric conversion element of Comparative Example 2 (described later) after being stored in the same manner as the photoelectric conversion element of Example 8 (hereinafter referred to as "ratio to Comparative Example 2"). Table 4 shows the retention rate (%) of the photoelectric conversion efficiency after 720 hours of storage from the initial photoelectric conversion efficiency measurement as an evaluation of durability.
[0331] [Example 9]
[0332] Using the compound (A-63) obtained in Synthesis Example 11 as a hole transport material for the photoelectric conversion element, a 50 mM chlorobenzene solution was prepared as a hole transport layer solution. Except that the hole transport layer solution used did not use lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as an additive and 4-tert-butylpyridine (0 mM) as an additive, the photoelectric conversion element was fabricated in the same manner as in Example 8, and the current-voltage characteristics were measured to obtain the initial photoelectric conversion efficiency. Furthermore, the above photoelectric conversion element was stored in a desiccator equipped with silica gel for 30 days from the initial photoelectric conversion efficiency measurement, and the current-voltage characteristics were measured again to obtain the photoelectric conversion efficiency after 30 days (720 hours). Table 3 shows the ratio of the photoelectric conversion efficiency after 720 hours of storage from the initial photoelectric conversion efficiency measurement to Comparative Example 2, and Table 4 shows the retention rate (%) of the photoelectric conversion efficiency after 720 hours of storage from the initial photoelectric conversion efficiency measurement as an evaluation of durability.
[0333] [Example 10]
[0334] Except for the use of compound (A-114), the photoelectric conversion element was fabricated in the same manner as in Example 8, and the current-voltage characteristics were measured to obtain the initial photoelectric conversion efficiency and the photoelectric conversion efficiency after 30 days (720 hours). Table 3 shows the ratio of the photoelectric conversion efficiency after 720 hours of storage from the initial photoelectric conversion efficiency measurement to that of Comparative Example 2, and Table 4 shows the retention rate (%) of the photoelectric conversion efficiency after 720 hours of storage from the initial conversion efficiency measurement as an evaluation of durability.
[0335] [Example 11]
[0336] Except for the use of compound (A-114), the photoelectric conversion element was fabricated in the same manner as in Example 9, and the current-voltage characteristics were measured to obtain the initial photoelectric conversion efficiency and the photoelectric conversion efficiency after 30 days (720 hours). Table 3 shows the ratio of the photoelectric conversion efficiency after 720 hours of storage from the initial conversion efficiency measurement to that of Comparative Example 1, and Table 4 shows the retention rate (%) of the photoelectric conversion efficiency after 720 hours of storage from the initial conversion efficiency measurement as an evaluation of durability.
[0337] [Example 12]
[0338] Except for the use of compound (A-115), the photoelectric conversion element was fabricated in the same manner as in Example 8, and the current-voltage characteristics were measured to obtain the initial photoelectric conversion efficiency and the photoelectric conversion efficiency after 30 days (720 hours). Table 3 shows the ratio of the photoelectric conversion efficiency after 720 hours of storage from the initial photoelectric conversion efficiency measurement to that of Comparative Example 2, and Table 4 shows the retention rate (%) of the photoelectric conversion efficiency after 720 hours of storage from the initial conversion efficiency measurement as an evaluation of durability.
[0339] [Example 13]
[0340] Except for the use of compound (A-115), the photoelectric conversion element was fabricated in the same manner as in Example 9, and the current-voltage characteristics were measured to obtain the initial photoelectric conversion efficiency and the photoelectric conversion efficiency after 30 days (720 hours). Table 3 shows the ratio of the photoelectric conversion efficiency after 720 hours of storage from the initial conversion efficiency measurement to that of Comparative Example 1, and Table 4 shows the retention rate (%) of the photoelectric conversion efficiency after 720 hours of storage from the initial conversion efficiency measurement as an evaluation of durability.
[0341] [Comparative Example 2]
[0342] Except for Spiro-OMeTAD (manufactured by Sigma-Aldrich), a common hole transport material shown by formula (B-1) in Comparative Example 1, the photoelectric conversion element was fabricated in the same manner as in Example 8, and the current-voltage characteristics were measured to obtain the initial photoelectric conversion efficiency and the photoelectric conversion efficiency after 30 days (720 hours). The initial photoelectric conversion efficiency was 13.2%. Table 4 shows the retention rate (%) of the photoelectric conversion efficiency after 720 hours of storage from the initial conversion efficiency measurement.
[0343] Table 3
[0344]
[0345] Table 4
[0346]
[0347] As shown in Table 3, compounds (A-63), (A-114), and (A-115) exhibit higher and more adequate photoelectric conversion efficiencies than the commonly used comparative compounds. This further demonstrates that compounds (A-63), (A-114), and (A-115) can be used as hole transport layers in photoelectric conversion devices even with reduced or no dopant. Therefore, photoelectric conversion devices containing compounds (A-63), (A-114), or (A-115) can reduce manufacturing costs by lowering the doping level, eliminating the need for doping operations, and can be fabricated with simpler processes and lower costs.
[0348] Furthermore, the results in Table 4 show that the photoelectric conversion element using a hole transport layer containing compound (A-63), compound (A-114), or compound (A-115) exhibits high photoelectric conversion efficiency even after 720 hours, and its retention rate is superior to that of the compounds in the comparative examples.
[0349] The present invention has been described in detail with reference to specific methods, but those skilled in the art can make various changes and modifications without departing from the concept and scope of the present invention.
[0350] Furthermore, this application is based on Japanese Patent Application No. 2020-129304, filed on July 30, 2020, the entire contents of which are incorporated herein by reference. All references cited herein are also incorporated in their entirety into this description.
[0351] By using the hole transport layer for photoelectric conversion elements of the present invention, it is effectively used in photoelectric conversion elements and perovskite solar cells that can efficiently extract current, have high efficiency and high durability, and can provide clean energy in the form of solar cells that can efficiently convert solar energy into electrical energy.
[0352] (Explanation of reference numerals in the attached diagram)
[0353] 1: Conductive support
[0354] 2: Cavity blocking layer
[0355] 3: Electron transport layer
[0356] 4: Photoelectric conversion layer
[0357] 5: Hole transport layer
[0358] 6: Counter electrode
[0359] 7: Conductive support
[0360] 8: Electron transport layer
[0361] 9: Photoelectric conversion layer
[0362] 10: Hole transport layer
[0363] 11: Counter electrode
Claims
1. A compound represented by the following general formula (1), wherein X in general formula (1) 1 and X 2 Each can be represented independently by the following general formula (2), 【Chemical Formula 1】 In the formula, R 1 and R 2 Each can be independently a methoxycarbonyl or an ethoxycarbonyl group. R 3 ~R 4 R 6 ~R 9 R 11 ~R 14 R 16 ~R 19 R 21 ~R 22 Each of these can independently represent a hydrogen atom, methoxy, ethoxy, propoxy, n-butoxy, n-pentoxy, n-hexoxy, heptaoxy, octoxy, nonoxy, decoxy, isopropoxy, isobutoxy, sec-butoxy, tert-butoxy, isooctoxy, or tert-octoxy. R 5 R 10 R 15 and R 20 Each of these can be independently methoxy, ethoxy, propoxy, n-butoxy, n-pentoxy, n-hexoxy, heptaoxy, octoxy, nonoxy, decoxy, isopropoxy, isobutoxy, sec-butoxy, tert-butoxy, isooctoxy, or tert-octoxy. [Chemical Formula 2] In the formula, R 23 ~R 28 Represents a hydrogen atom. Y 1 This represents a sulfur atom, where m and n represent integers from 0 to 2, respectively. in, Either m or n is 1.
2. The compound according to claim 1, wherein, In the general formula (2), m is 1.
3. A compound having the following structure: 【Chemical Formula 3】 [Chemical Formula 4] [Chemical Formula 5] 【Chemical Formula 6】 。 4. A hole transport material for a photoelectric conversion element, comprising the compound according to any one of claims 1 to 3.
5. A hole transport layer formed of a composition comprising a hole transport material for a photoelectric conversion element as claimed in claim 4 and a dopant as an additive, wherein the dopant is in an equivalent amount of 0 to 0.5 equivalents relative to the hole transport material for the photoelectric conversion element.
6. A photoelectric conversion element comprising the hole transport layer as described in claim 5.
7. A solar cell comprising the photoelectric conversion element of claim 6.
Citation Information
Patent Citations
Data processing method and data processor
JP2020129304A
Complex and perovskite material, and perovskite-type solar cell using complex or perovskite material
WO2017104792A1
Organic photoelectric material containing thiophene structure and application thereof
CN109438469A
